N-vinyl lactam copolymer and composition

Through the designed N-vinyl lactam-based copolymer, the battery performance problems caused by the dissolution of polyvinylpyrrolidone in the battery electrolyte are solved, and excellent results are achieved in the solubility and carbon dispersion ability in water.

CN119452001APending Publication Date: 2025-02-14NIPPON SHOKUBAI CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380047411.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-27
Filing Date
2023-06-02
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Polyvinylpyrrolidone is dissolved in the carbonate electrolyte solvent of the battery, resulting in hindering the battery performance. At the same time, the existing copolymer has low solubility in water, and is only suitable for positive electrode materials.

Method used

By using the N-vinyl lactam-based copolymer composed of specific components, its solubility in water and carbon dispersion ability are ensured, while the amount of dissolution in the carbonate electrolyte solvent is reduced. The copolymer contains structural units from the salt of the acid-based monomer and the N-vinyl lactam-based monomer, and the composition ratio and weight average molecular weight of the structural units are within a predetermined range.

Benefits of technology

High solubility in water and low dissolution in carbonate electrolyte solvents are achieved, excellent carbon dispersion ability is maintained, and obstacles to battery performance are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005189891350000061
    Figure BDA0005189891350000061
  • Figure BDA0005189891350000121
    Figure BDA0005189891350000121
  • Figure BDA0005189891350000281
    Figure BDA0005189891350000281
Patent Text Reader

Abstract

The purpose of the present invention is to provide an N-vinyllactam copolymer and a composition which are capable of maintaining excellent carbon dispersibility and solubility in water and which are less eluted in a carbonate electrolyte solvent. The present invention pertains to an N-vinyl lactam copolymer having a structural unit (A) derived from a salt of an acid group-containing monomer and a structural unit (B) derived from an N-vinyl lactam monomer, the content of the structural unit (A) being 30% by mass or less when the total amount of the structural units (A) and (B) is 100% by mass, and the content of the structural unit (B) being 30% by mass or less when the total amount of the structural units (A) and (B) is 100% by mass. The N-vinyl lactam copolymer has a weight average molecular weight of 1,000 to 100,000 (inclusive), and a K value, as determined by the Fikentscher method, of 12 to 60.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to N-vinyl lactam-based copolymers and compositions. Background Art

[0002] N-vinyl lactam polymers, such as polyvinyl pyrrolidone, are used in a wide range of fields as water-soluble and safe functional polymers, such as cosmetics, pharmaceutical and pesticide intermediates, food additives, photosensitive electronic materials, tackifiers, various special industrial uses (such as the manufacture of hollow fiber membranes), and battery materials.

[0003] As a positive electrode paste for a battery, there has been reported a paste characterized by using a copolymer of stearyl methacrylate, methoxypolyethylene glycol methacrylate, and methacrylamide (see Patent Document 1).

[0004] In addition, as a dispersant for a carbon material, a method characterized by using a copolymer containing acrylonitrile and N-vinylpyrrolidone has been reported (see Patent Document 2).

[0005] Furthermore, there is a report on a carbon nanotube dispersion for an electrode, which is characterized by using carbon nanotubes, polyvinyl pyrrolidone, N-methyl-2-pyrrolidone, and an amine compound (see Patent Document 3).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2018-170218

[0009] Patent Document 2: Japanese Patent Application Publication No. 2016-65142

[0010] Patent Document 3: Japanese Patent No. 6531926 Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, although polyvinyl pyrrolidone has excellent carbon dispersion ability, it has the problem of dissolving into the carbonate electrolyte solvent of the battery and hindering the battery performance. In addition, the copolymers recorded in these patent documents have the following problems: although the dissolution into the electrolyte solvent can be suppressed, the solubility in water is low and can only be used in the positive electrode material.

[0013] Therefore, an object of the present disclosure is to provide an N-vinyllactam-based copolymer and a composition which maintain excellent carbon dispersibility and solubility in water and have little elution in a carbonate-based electrolyte solvent.

[0014] Means for solving problems

[0015] The inventors of the present invention have conducted in-depth research and found that by using specified components as monomers constituting N-vinyl lactam copolymers and making their composition ratio within a specified range, excellent carbon dispersion ability and solubility in water can be maintained, and dissolution in the above-mentioned electrolyte solvent can be reduced. It is thought that the above-mentioned scheme can satisfactorily solve the above-mentioned problems, thereby realizing the present invention.

[0016] The present invention includes the following N-vinyl lactam-based copolymers and the like.

[0017] [1] An N-vinyl lactam copolymer comprising a structural unit (A) derived from a salt of an acid group-containing monomer and a structural unit (B) derived from an N-vinyl lactam monomer, wherein the content of the structural unit (A) is 30% by mass or less, when the total amount of the structural unit (A) and the structural unit (B) is 100% by mass, and the weight average molecular weight of the N-vinyl lactam copolymer is 1,000 to 100,000, and the K value obtained by the Fikentscher method is 12 to 60.

[0018] [2] The N-vinyllactam copolymer according to [1] above, wherein the structural unit (A) derived from the salt of an acid group-containing monomer is a structural unit (A1) derived from the salt of a carboxyl group-containing monomer and / or a structural unit (A2) derived from the salt of a sulfonic acid group-containing monomer.

[0019] [3] The N-vinyllactam copolymer according to [1] or [2], wherein, when the structural unit (A) contains the structural unit (A1), the content of the structural unit (A1) is 15% by mass or less relative to 100% by mass of the total amount of the structural unit (A) and the structural unit (B).

[0020] [4] The N-vinyllactam copolymer as described in any one of [1] to [3] above, wherein, when the structural unit (A) contains the structural unit (A2), the content of the structural unit (A2) is 30% by mass or less relative to 100% by mass of the total amount of the structural unit (A) and the structural unit (B).

[0021] [5] The N-vinyllactam copolymer according to any one of [1] to [4] above, wherein the solubility in water is 1% by mass or more.

[0022] [6] The N-vinyllactam copolymer according to any one of [1] to [5] above, wherein the solubility in the electrolyte solvent is 1% by mass or less.

[0023] [7] The N-vinyllactam copolymer according to any one of [1] to [6] above, wherein the weight average molecular weight is 5,000 to 100,000.

[0024] [8] The N-vinyllactam copolymer according to any one of [1] to [7], wherein the structural unit (A1) derived from the salt of a carboxyl group-containing monomer is a structural unit derived from at least one compound selected from the group consisting of lithium acrylate, sodium acrylate, potassium acrylate and ammonium acrylate.

[0025] [9] The N-vinyllactam copolymer according to any one of [1] to [8], wherein the structural unit (A2) derived from the salt of the sulfonic acid group-containing monomer is a structural unit derived from at least one compound selected from the group consisting of 2-acrylamide-2-methyl-1-propanesulfonic acid (sodium, lithium, potassium, ammonium), 2-hydroxy-3-allyloxypropanesulfonic acid (sodium, lithium, potassium, ammonium), 2-sulfoethylmethacrylic acid (sodium, lithium, potassium, ammonium), vinylsulfonic acid (sodium, lithium, potassium, ammonium) and p-styrenesulfonic acid (sodium, lithium, potassium, ammonium).

[0026]

[10] A composition comprising an N-vinyllactam copolymer and a carbon material, wherein the N-vinyllactam copolymer has a structural unit (A) derived from a salt of an acid group-containing monomer and a structural unit (B) derived from an N-vinyllactam monomer.

[0027]

[11] The composition according to

[10] above, comprising N-methyl-2-pyrrolidone and / or water.

[0028]

[12] The composition according to

[10] or

[11] above, wherein the carbon material is one or more selected from carbon black, carbon nanofibers, and carbon nanotubes.

[0029]

[13] The composition as described in any one of

[10] to

[12] above, wherein the structural unit (A) derived from the salt of the acid group-containing monomer is a structural unit (A1) derived from the salt of the carboxyl group-containing monomer and / or a structural unit (A2) derived from the salt of the sulfonic acid group-containing monomer.

[0030]

[14] The composition according to any one of

[10] to

[13] above, wherein the structural unit (A) derived from a salt of an acid group-containing monomer is a structural unit (A1) derived from a salt of a carboxyl group-containing monomer.

[0031]

[15] A method for producing an N-vinyllactam copolymer, which is a method for producing the N-vinyllactam copolymer described in any one of [1] to [9] above, wherein the method comprises a step of polymerizing a monomer component comprising a salt of an acid group-containing monomer and an N-vinyllactam monomer.

[0032] Effects of the Invention

[0033] According to the present disclosure, it is possible to provide an N-vinyllactam-based copolymer and a composition which maintain excellent carbon dispersibility and solubility in water and have little elution in a carbonate-based electrolyte solvent. DETAILED DESCRIPTION

[0034] The following description of the preferred embodiments is merely illustrative in nature and is not intended to limit the present disclosure, its applications, or uses.

[0035] It should be noted that, in the following description, unless otherwise specified, "%" means "mass %", "parts" means "mass parts", and "A to B" indicating a range means A or more and B or less. In addition, in the present disclosure, "(meth)acrylate" means "acrylate" or "methacrylate", and "(meth)acrylic acid" means "acrylic acid" or "methacrylic acid".

[0036] [N-vinyl lactam copolymer]

[0037] The N-vinyl lactam copolymer disclosed herein comprises a structural unit (A) derived from a salt of an acid group-containing monomer and a structural unit (B) derived from an N-vinyl lactam monomer, wherein the content of the structural unit (A) is 30% by mass or less, when the total amount of the structural unit (A) and the structural unit (B) is 100% by mass, the weight average molecular weight is 1,000 to 100,000, and the K value obtained by the Fikentscher method is 12 to 60.

[0038] Thus, the N-vinyl lactam copolymer disclosed in the present invention maintains solubility in water and has little dissolution in carbonate electrolyte solvents. In addition, the existing polymers disclosed in Patent Documents 1 to 3 may also hinder battery performance due to insufficient dispersibility in the dispersion of the carbon material used as the positive electrode material and the increase in the amount of impurities such as residual monomers. In contrast, in the above-mentioned N-vinyl lactam copolymer, the amount of impurities such as residual monomers is reduced, and the balance between the electrostatic repulsion caused by the salt of the acid group and the adsorption of N-vinyl lactam to carbon is good, so the dispersibility of the carbon material is also excellent.

[0039] The acid group-containing monomer (precursor of the salt of the acid group-containing monomer) may be any compound as long as it has an acid group and an ethylenically unsaturated hydrocarbon group.

[0040] The acid group is not particularly limited, and examples thereof include a carboxyl group, a sulfonic acid group, a phosphoric acid group, etc. The acid group is preferably a carboxyl group or a sulfonic acid group.

[0041] Examples of the acid group-containing monomer include a carboxyl group-containing monomer, a sulfonic acid group-containing monomer, and a phosphoric acid group-containing monomer.

[0042] As the above-mentioned carboxyl group-containing monomer, there is no particular limitation as long as it has a carboxyl group and an ethylenically unsaturated hydrocarbon group, and examples thereof include unsaturated monocarboxylic acid monomers such as (meth) acrylic acid, crotonic acid, tiliac acid, 3-methyl crotonic acid, 2-methyl-2-pentenoic acid, and itaconic acid, and unsaturated dicarboxylic acid monomers such as maleic acid, itaconic acid, mesaconic acid, citraconic acid, fumaric acid, and 2-methyleneglutaric acid. Among them, (meth) acrylic acid and maleic acid are preferred, and (meth) acrylic acid is more preferred.

[0043] The sulfonic acid group-containing monomer is not particularly limited as long as it has a sulfonic acid group and an ethylenically unsaturated hydrocarbon group. Examples thereof include 2-acrylamide-2-methyl-1-propanesulfonic acid, 2-hydroxy-3-allyloxypropanesulfonic acid, 2-sulfoethyl methacrylic acid, p-styrenesulfonic acid, 2-(meth)allyloxyethylenesulfonic acid, α-methylp-styrenesulfonic acid, vinylsulfonic acid, vinylaminosulfonic acid, (meth)allylsulfonic acid, isoprenesulfonic acid, 4-(allyloxy)benzenesulfonic acid, 1-methyl-2-propene-1-sulfonic acid, 1,1-dimethyl-2-propene-1-sulfonic acid, 3-butene-1-sulfonic acid, 1-butene-3-sulfonic acid, 2-acrylamide-1-methylpropanesulfonic acid, 2-acrylamidepropanesulfonic acid, 2-acrylamide-n-butanesulfonic acid, 2-acrylamide-2-phenylpropanesulfonic acid, and 2-((meth)acryloyloxy)ethanesulfonic acid. Among them, 2-acrylamide-2-methyl-1-propanesulfonic acid, 2-hydroxy-3-allyloxypropanesulfonic acid, 2-sulfoethylmethacrylic acid, vinylsulfonic acid, and p-styrenesulfonic acid are preferred, and 2-acrylamide-2-methyl-1-propanesulfonic acid is more preferred.

[0044] As the above-mentioned phosphoric acid group-containing monomer, there is no particular limitation as long as it has a phosphoric acid group and an ethylenically unsaturated hydrocarbon group, and examples thereof include (meth)acryloxyalkyl phosphates such as (meth)acryloxyethyl phosphate and (meth)acryloxyisopropyl phosphate; alkenyl phosphates such as vinyl phosphate, allyl phosphate, propenyl phosphate, isopropenyl phosphate, butenyl phosphate, pentenyl phosphate, octenyl phosphate, decenyl phosphate and dodecenyl phosphate; and the like.

[0045] The N-vinyl lactam copolymer of the present disclosure preferably has a structural unit (A1) derived from a salt of a carboxyl group-containing monomer and / or a structural unit (A2) derived from a salt of a sulfonic acid group-containing monomer. More preferably, it has the structural unit (A1).

[0046] The N-vinyl lactam copolymer disclosed herein has a structural unit derived from a (meth) acrylic acid salt as a salt of a carboxyl group-containing monomer, which is one of the preferred embodiments of the present invention. In this case, acrylic acid and / or methacrylic acid can be used as a precursor (monomer) before polymerization, and the acrylic acid and / or methacrylic acid in the obtained N-vinyl lactam copolymer only need to be a salt of a carboxylic acid without containing an acid form.

[0047] The method for producing the N-vinyl lactam copolymer disclosed herein is not particularly limited, and a salt of an acidic monomer such as (meth)acrylate may be used as a monomer component, or an unneutralized acidic monomer may be used, and a neutralized salt may be prepared by neutralization treatment after the polymerization reaction. For the reason that the amount of impurities such as residual monomers can be reduced, a salt of an acidic monomer such as (meth)acrylate is preferably used as a monomer component.

[0048] The structural unit (A) derived from the salt of the acid group-containing monomer has the same structure as the structural unit in which the polymerizable carbon-carbon double bond group of the salt of the acid group-containing monomer is converted into a single bond.

[0049] When the structural unit (A) is a structural unit derived from a (meth)acrylate, the structural unit (A) of the present disclosure includes the case where a monomer such as acrylamide or acrylonitrile is used, and a carboxylate is obtained by performing a polymerization reaction, hydrolysis, and then a neutralization reaction.

[0050] The (meth)acrylic acid is not particularly limited as long as it is one or more selected from acrylic acid and methacrylic acid. Acrylic acid is preferred. If the structural unit derived from (meth)acrylate is a structural unit derived from acrylate, the N-vinyl lactam copolymer disclosed in the present invention can more fully reduce the amount of residual monomers contained, and can adjust the solubility in water and electrolyte solvents as designed, which is preferred from this aspect.

[0051] The N-vinyl lactam copolymer disclosed herein has a structural unit (A) derived from a salt of an acid group-containing monomer, and examples of the salt include alkali metal salts, alkaline earth metal salts, ammonium salts, organic ammonium salts, organic amine salts, etc. There are no particular limitations as long as the salt is one or more selected from these salts.

[0052] Examples of the alkali metal salt include lithium salt, sodium salt, potassium salt, etc. Examples of the alkaline earth metal salt include calcium salt, magnesium salt, etc.

[0053] Examples of the organic ammonium salt include methylammonium salt, ethylammonium salt, dimethylammonium salt, diethylammonium salt, trimethylammonium salt, and triethylammonium salt.

[0054] Examples of the organic amine salt include ethanolamine salts, diethanolamine salts, triethanolamine salts, monoisopropanolamine salts, diisopropanolamine salts, triisopropanolamine salts, hydroxyethyldiisopropanolamine salts, dihydroxyethylisopropanolamine salts, tetrakis(2-hydroxypropyl)ethylenediamine, penta(2-hydroxypropyl)diethylenetriamine and other alkanolamine salts. Among these, diethanolamine salts, diisopropanolamine salts, triisopropanolamine salts, hydroxyethyldiisopropanolamine salts, tetrakis(2-hydroxypropyl)ethylenediamine salts, penta(2-hydroxypropyl)diethylenetriamine salts are preferred, and diethanolamine salts, triisopropanolamine salts, and hydroxyethyldiisopropanolamine salts are more preferred.

[0055] The above-mentioned salt is preferably an alkali metal salt, an alkaline earth metal salt, or an ammonium salt, more preferably an alkali metal salt or an ammonium salt, and still more preferably a lithium salt, a sodium salt, a potassium salt, or an ammonium salt.

[0056] Lithium salts and sodium salts are particularly preferred.

[0057] When the salt is the above-mentioned salt, the withstand voltage of the N-vinyl lactam copolymer of the present disclosure is good and the generation of volatile substances can be suppressed, so that the impairment of battery performance can be more sufficiently suppressed, which is preferable.

[0058] The structural unit derived from the (meth)acrylate can be represented by the following general formula (1).

[0059] [Chemistry 1]

[0060]

[0061] (In general formula (1), R 1 represents at least one selected from metal atoms, ammonium salts, organic ammonium salts, and organic amine salts. 2 It is a hydrogen atom and a methyl group.

[0062] The asterisks represent atoms contained in other structural units of the same or different types to which the structural unit represented by the general formula (1) is bonded.

[0063] In the above general formula (1), R 1 There is no particular limitation as long as it is one or more selected from metal atoms, ammonium salts, organic ammonium salts, and organic amine salts, and the preferred embodiments are the same as those described above for the salts. 2 There is no particular limitation as long as it is a hydrogen atom and / or a methyl group, and the preferred embodiment is as described above.

[0064] Another preferred embodiment of the structural unit derived from (meth)acrylate is a structural unit derived from at least one compound selected from the group consisting of lithium acrylate, sodium acrylate, potassium acrylate, and ammonium acrylate, and more preferably at least one compound selected from lithium acrylate and sodium acrylate.

[0065] When the structural unit derived from the (meth)acrylate salt is a structural unit derived from the above-mentioned monomer, it is possible to exhibit excellent effects in that the amount of impurities can be more sufficiently reduced and the inhibition of battery performance due to impurities can be more sufficiently suppressed.

[0066] An aspect in which the N-vinyl lactam-based copolymer disclosed in the present invention has a structural unit (A2) derived from a salt of a sulfonic acid group-containing monomer is also one of the preferred embodiments of the present invention.

[0067] The structural unit (A2) derived from the salt of the sulfonic acid group-containing monomer is preferably a structural unit derived from at least one compound selected from the group consisting of 2-acrylamide-2-methyl-1-propanesulfonic acid (sodium, lithium, potassium, ammonium), 2-hydroxy-3-allyloxypropanesulfonic acid (sodium, lithium, potassium, ammonium), 2-sulfoethylmethacrylic acid (sodium, lithium, potassium, ammonium), vinylsulfonic acid (sodium, lithium, potassium, ammonium), and p-styrenesulfonic acid (sodium, lithium, potassium, ammonium). More preferably, it is a structural unit derived from 2-acrylamide-2-methyl-1-propanesulfonic acid (sodium, lithium, potassium, ammonium).

[0068] The structural unit (B) derived from the N-vinyllactam monomer is not particularly limited as long as the structural unit derived from the monomer is contained as the structural unit (B) in the N-vinyllactam copolymer of the present disclosure by polymerization reaction of the N-vinyllactam monomer.

[0069] In other manifestations, the N-vinyllactam-based monomer is a precursor of a structural unit derived from an N-vinyllactam-based monomer.

[0070] The N-vinyllactam monomer is a monomer having a cyclic lactam ring, and examples thereof include N-vinyl-2-pyrrolidone, N-vinyl caprolactam, N-vinyl-4-butylpyrrolidone, N-vinyl-4-propylpyrrolidone, N-vinyl-4-ethylpyrrolidone, N-vinyl-4-methylpyrrolidone, N-vinyl-4-methyl-5-ethylpyrrolidone, N-vinyl-4-methyl-5-propylpyrrolidone, N-vinyl-5-methyl-5-ethylpyrrolidone, N-vinyl-5-propylpyrrolidone, N-vinyl-5-butylpyrrolidone, N-vinyl-4-methylcaprolactam, N-vinyl-6-methylcaprolactam, N-vinyl-6-propylcaprolactam, and N-vinyl-7-butylcaprolactam. Among these, N-vinyl-2-pyrrolidone and / or N-vinylcaprolactam are preferably used because of good polymerizability, good color stability of the obtained polymer at high temperature, and good solubility in solvents. It should be noted that the above-mentioned N-vinyl lactam monomers can be used alone or in combination of two or more.

[0071] The N-vinyl lactam copolymer disclosed in the present invention has a structural unit (A) derived from a salt of an acid group-containing monomer and a structural unit (B) derived from an N-vinyl lactam monomer as essential units, and when the total amount of the structural unit (A) and the structural unit (B) is set to 100% by mass, the content of the structural unit (A) is 30% by mass or less. If the content of the structural unit (A) is within the above range, dissolution in the electrolyte solvent can be suppressed, and the dispersibility of the carbon material is good. In addition, the content of the structural unit (A) preferably contains 0.1% by mass or more, more preferably 1% by mass or more, and further preferably 1.5% by mass or more.

[0072] The content of the structural unit (A) within the above range is preferred from the viewpoint of being able to more fully suppress dissolution in the electrolyte solvent and improving the dispersibility of the carbon material.

[0073] The content of the structural unit (A) is preferably 25% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less.

[0074] The content of the structural unit (A) is preferably 0.1 to 30% by mass, more preferably 1 to 25% by mass, further preferably 1.5 to 20% by mass, particularly preferably 2 to 15% by mass.

[0075] In one embodiment, the content of the structural unit (A) may be 12% by mass or less, less than 10% by mass, or 5% by mass or less.

[0076] When the content of the structural unit (A) is within the above range, it is preferred from the viewpoint of good solubility in N-methyl-2-pyrrolidone.

[0077] When the N-vinyllactam copolymer of the present disclosure has the structural unit (A1), the content of the structural unit (A1) is preferably 0.1 to 15% by mass, more preferably 1 to 13% by mass, and even more preferably 1.5 to 10% by mass, based on 100% by mass of the total amount of the structural unit (A) and the structural unit (B).

[0078] When the N-vinyl lactam copolymer of the present disclosure has a structural unit (A2), the content of the structural unit (A2) is preferably 5 to 30% by mass, more preferably 8 to 25% by mass, and even more preferably 10 to 22% by mass, based on 100% by mass of the total amount of the structural unit (A) and the structural unit (B).

[0079] In addition, when the total amount of the above-mentioned structural unit (A) and the above-mentioned structural unit (B) is set to 100 mass%, the content of the structural unit (A) derived from the salt of the acid group-containing monomer can be 30 mass% or less, but it is preferred that the total content of the structural unit (A) and the structural unit derived from the acid-type acid group-containing monomer is 30 mass% or less.

[0080] The total content of the structural unit (A) and the structural unit derived from the acidic acid group-containing monomer is preferably 0.1% by mass or more, more preferably 1% by mass or more, and even more preferably 1.5% by mass or more.

[0081] The total content of the structural unit (A) and the structural unit derived from the acidic acid group-containing monomer is more preferably 25% by mass or less, further preferably 20% by mass or less, and particularly preferably 15% by mass or less.

[0082] The total content of the structural unit (A) and the structural unit derived from the acidic acid group-containing monomer is preferably 0.1 to 30 mass %, more preferably 1 to 25 mass %, further preferably 1.5 to 20 mass %, particularly preferably 2 to 15 mass %.

[0083] In one embodiment, the total content of the structural unit (A) and the structural unit derived from the acid-type acid group-containing monomer may be 12% by mass or less, less than 10% by mass, or 5% by mass or less.

[0084] The content of the structural unit (B) in the N-vinyl lactam copolymer disclosed herein is 70% by mass or more, preferably 70 to 99.9% by mass, more preferably 75 to 99% by mass, further preferably 80 to 98.5% by mass, and particularly preferably 85 to 98% by mass, relative to 100% by mass of the total amount of the structural unit (A) and the structural unit (B).

[0085] The N-vinyl lactam copolymer disclosed in the present invention is not particularly limited as long as it has the structural unit (A) derived from the salt of the acid group-containing monomer and the structural unit (B) derived from the N-vinyl lactam monomer as essential units, and may also contain the structural unit (E) derived from other monomers. Specifically, the monomers that are precursors of the structural units derived from other monomers include: acid-type carboxyl-containing monomers such as (meth)acrylic acid, maleic acid, fumaric acid, itaconic acid, crotonic acid, and 2-methyleneglutaric acid (excluding salts of carboxyl-containing monomers); (meth)acrylic acid alkyl esters containing hydroxyl groups such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and α-hydroxymethylethyl (meth)acrylate; (meth)acrylic acid alkyl esters containing hydroxyl groups such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and α-hydroxymethylethyl (meth)acrylate; Alkyl (meth)acrylates which are esters of an alkyl group having 1 to 18 carbon atoms of (meth)acrylic acid, such as methyl acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate; alkoxyalkyl (meth)acrylates such as methoxymethyl (meth)acrylate and methoxyethyl (meth)acrylate; amino group-containing acrylic acid esters such as dimethylaminoethyl (meth)acrylate or a quaternary ammonium product thereof; (meth)acrylamide, dimethylacrylamide, isopropylacrylamide, and the like Monomers containing amide groups; vinyl esters such as vinyl acetate; olefins such as ethylene and propylene; aromatic vinyl monomers such as styrene; maleimide derivatives such as maleimide, phenylmaleimide, and cyclohexylmaleimide; vinyl monomers containing nitrile groups such as (meth)acrylonitrile; acid-type monomers containing sulfonic acid groups such as 3-allyloxy-2-hydroxypropanesulfonic acid, 2-acrylamide-2-methylpropanesulfonic acid, styrenesulfonic acid, and vinylsulfonic acid (excluding salts of sulfonic acid-containing monomers); acid-type monomers containing phosphonic acid such as vinylphosphonic acid and (meth)allylphosphonic acid Acid group monomers (excluding salts of phosphoric acid group-containing monomers); (meth) acrolein and other vinyl monomers containing aldehyde groups; alkyl vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, butyl vinyl ether; vinyl chloride, vinylidene chloride, allyl alcohol and other monomers containing other functional groups; polyalkylene glycol (meth) acrylate, monoalkoxy polyalkylene glycol (meth) acrylate, vinyl alcohol, (meth) allyl alcohol, isoprene alcohol and other monomers having a structure in which 1 to 300 moles of alkylene oxide are added to an unsaturated alcohol, etc. Monomers containing polyalkylene glycol chains; etc. These other monomers can be used alone or in combination of two or more. It should be noted that the description of carboxylates, sulfonates, and phosphonates (salts) is the same as the above-mentioned salts. The preferred embodiment is also the same. As a structural unit (E) derived from other monomers, a monomer containing a polyalkylene glycol chain is preferred from the perspective of being able to impart steric repulsion performance and improving the dispersion stability of carbon materials in a low concentration system.In addition, vinyl monomers containing a nitrile group such as (meth)acrylonitrile and acrylates containing an amino group are preferred from the viewpoint of being able to impart adsorption properties to carbon and improving the carbon dispersion stability in a high-concentration system.

[0086] The average number of moles of alkylene oxide added in the polyalkylene glycol chain-containing monomer is not particularly limited, but is preferably 1 to 100, more preferably 1 to 50, further preferably 1 to 30, and particularly preferably 1 to 20.

[0087] As the above-mentioned alkylene oxide, for example, ethylene oxide, propylene oxide, butylene oxide, isobutylene oxide, 2,3-butylene oxide, styrene oxide, and alkylene oxides having 2 to 10 carbon atoms can be cited. More preferred are alkylene oxides having 2 to 4 carbon atoms such as ethylene oxide, propylene oxide, and butylene oxide, and further preferred are ethylene oxide and propylene oxide. It should be noted that the oxyalkylene group represented by AO is not limited to the group formed by the addition reaction of alkylene oxide. In addition, when the above-mentioned polyalkylene glycol is a product of two or more alkylene oxide adducts, it can be any of random addition, block addition, alternating addition, etc. As the oxyalkylene group in the polyalkylene glycol chain, it is preferred to have oxyethylene as an essential component, more preferably 50 mol% or more of oxyethylene, and further preferably 90 mol% or more of oxyethylene.

[0088] In the case where the above-mentioned other structural units (E) are included in the N-vinyl lactam copolymer of the present disclosure, when the total amount of the above-mentioned structural units (A), the above-mentioned structural units (B) and the other structural units (E) is set to 100% by mass, the content of the above-mentioned structural units (E) is preferably 50% by mass or less. More preferably, it is 30% by mass or less, further preferably 20% by mass or less, and further more preferably 10% by mass or less. In one embodiment, the content of the above-mentioned monomer (E) is preferably 5% by mass or less, more preferably 2% by mass or less, and particularly preferably 0% by mass.

[0089] In the N-vinyl lactam copolymer disclosed in the present invention, the mode in which 0.1 to 30% by mass of the structural unit derived from the monomer containing the polyalkylene glycol chain is contained relative to 100% by mass of the total amount of the structural unit (A), the structural unit (B) and the other structural units (E) is one of the preferred embodiments of the present invention. The content ratio of the structural unit derived from the monomer containing the polyalkylene glycol chain is more preferably 1 to 30% by mass, further preferably 5 to 25% by mass, and particularly preferably 10 to 25% by mass.

[0090] In the N-vinyl lactam copolymer disclosed in the present invention, the mode having 0.1 to 30% by mass of structural units derived from vinyl monomers containing nitrile groups such as (meth) acrylonitrile relative to the total amount of 100% by mass of the structural units (A), the structural units (B) and other structural units (E) is one of the preferred embodiments of the present invention. The content ratio of the structural units derived from vinyl monomers containing nitrile groups is more preferably 1 to 25% by mass, further preferably 3 to 20% by mass, and particularly preferably 5 to 15% by mass.

[0091] The N-vinyl lactam copolymer of the present invention may have a phosphorus atom. Regarding the phosphorus atom, for example, as described below, by using a phosphorus compound such as hypophosphorous acid (salt) as a reducing agent during the production of the N-vinyl lactam copolymer of the present invention, a phosphorus atom can be introduced into the main chain of the N-vinyl lactam copolymer of the present invention.

[0092] Phosphorus atom can be contained in N-vinyl lactam copolymer in the form of structural unit containing phosphorus atom.By having structural unit containing phosphorus atom in the main chain, coloring (yellowing) when heating N-vinyl lactam copolymer can be suppressed to be lower.Here, as the structural unit containing phosphorus in the main chain, for example, hypophosphite (salt) group (referring to hypophosphite or hypophosphite group), phosphite (salt) group (referring to phosphite or phosphite group) etc. can be cited, preferably at least one selected from the group consisting of them.More specifically, phosphonic acid (salt) group, phosphinic acid (salt) group etc. can be cited.Among these, phosphinic acid (salt) group is preferred.That is, N-vinyl lactam copolymer of the present disclosure can have phosphinic acid (salt) group in the main chain.

[0093] Examples of the salt include metal salts, ammonium salts, and organic amine salts, preferably metal salts. Examples of the metal salt include alkali metal salts such as lithium salts, sodium salts, and potassium salts; alkaline earth metal salts such as calcium salts and magnesium salts; transition metal salts; and preferably alkali metal salts.

[0094] It should be noted that, when the above-mentioned structural unit comprising phosphorus atom is the structural unit containing hypophosphite, phosphite or their metal salt groups, for example, hypophosphite (salt) group and / or phosphite (salt) group can be formed in the main chain of polymer, and then converted into desired acid or metal salt by adding acid or alkali. Similarly, it is also possible to convert by utilizing ion exchange resin etc. to process.

[0095] In the N-vinyl lactam copolymer of the present invention having a structural unit containing a phosphorus atom in the above-mentioned main chain, the content ratio of the structural unit containing a phosphorus atom in the above-mentioned main chain is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and further preferably 0.1% by mass or more, relative to the total mass of 100% by mass of the N-vinyl lactam copolymer of the present invention. In addition, it is preferably 10% by mass or less, more preferably 7% by mass or less, and further preferably 6% by mass or less. It should be noted that, in the case of calculating the mass % of the structural unit containing phosphorus in the main chain relative to the total mass of the N-vinyl lactam copolymer of the present invention, when the above-mentioned situation is met, the calculation is also performed by acid conversion or amine conversion. The above-mentioned phosphorus atom introduced into the main chain of the N-vinyl lactam copolymer of the present invention, or the above-mentioned structural unit containing a phosphorus atom, can be, for example, 31 The results were determined by P-NMR analysis.

[0096] The N-vinyl lactam copolymer disclosed in the present invention may have a functional group such as an aldehyde group, a carboxyl group, a hydroxyl group, or an amino group at the terminal.

[0097] When the N-vinyllactam copolymer of the present disclosure has a structural unit derived from vinylpyrrolidone at the terminal, it can be represented by the following general formula (2).

[0098] [Chemistry 2]

[0099]

[0100] (In the formula, Z represents a group containing an aldehyde group, a carboxyl group, a hydroxyl group or an amino group. The asterisk represents an atom contained in another structural unit to which the structural unit derived from vinyl pyrrolidone is bonded)

[0101] The structure represented by the general formula (2) can be introduced, for example, by using hydrogen peroxide as a polymerization initiator and a base such as ammonia as a pH adjuster when producing the N-vinyllactam copolymer of the present disclosure as described below.

[0102] The phosphorus atoms in the above-mentioned copolymer can be introduced, for example, by using a phosphorus compound such as hypophosphorous acid (salt) as a reducing agent when producing the N-vinyl lactam copolymer of the present invention as described below. When phosphorus compounds are difficult to obtain, the N-vinyl lactam copolymer of the present invention preferably has a structure represented by the above-mentioned general formula (2).

[0103] The N-vinyl lactam copolymer disclosed herein is not particularly limited as long as the weight average molecular weight is 1,000 to 100,000, preferably 3,000 to 90,000, more preferably 5,000 to 80,000, further preferably 7,000 to 70,000, particularly preferably 8,000 to 60,000, and most preferably 10,000 to 50,000.

[0104] When the weight average molecular weight of the N-vinyl lactam copolymer disclosed in the present invention is within the above range, it is preferred from the viewpoint of being excellent in the ability to disperse the carbon material and being able to suppress the increase in viscosity of the carbon material dispersion.

[0105] In addition, as the value of the weight average molecular weight of the lactam group-containing copolymer of the present disclosure, a value measured by the method described in the later-mentioned Examples is adopted.

[0106] The K value of the N-vinyl lactam copolymer disclosed in the present invention obtained by the Fikentscher method is 12 to 60. It is preferably 55 or less, and more preferably 50 or less. If the K value is in the above range, it is preferred from the perspective of being able to suppress the viscosity increase of the carbon material dispersion. In addition, the K value of the N-vinyl lactam copolymer disclosed in the present invention obtained by the Fikentscher method is preferably 20 or more. It is more preferably 23 or more, and further preferably 25 or more. If the K value is in the above range, it is preferred from the perspective of excellent dispersibility of the carbon material.

[0107] In addition, as the K value of the lactam group-containing copolymer of the present disclosure based on the Fikentscher method, a value measured by the method described in the later-described Examples is adopted.

[0108] The solubility of the N-vinyl lactam copolymer disclosed in the present invention in N-methyl-2-pyrrolidone is preferably 1% by mass or more. The solubility in N-methyl-2-pyrrolidone of 1% by mass or more means that at 25° C. and atmospheric pressure, 1 g or more of the N-vinyl lactam copolymer disclosed in the present invention is dissolved in 100 g of N-methyl-2-pyrrolidone.

[0109] It is preferably 1.2 mass % or more, more preferably 1.5 mass % or more, and even more preferably 2 mass % or more.

[0110] When the solubility of the N-vinyl lactam copolymer disclosed herein in N-methyl-2-pyrrolidone is within the above range, it is preferably used as a carbon material dispersant in N-methyl-2-pyrrolidone, for example, as a carbon material dispersant in a positive electrode paste for a battery.

[0111] The solubility of the N-vinyl lactam copolymer disclosed herein in water is preferably 1% by mass or more. A solubility of 1% by mass or more in water means that 1 g or more of the N-vinyl lactam copolymer disclosed herein dissolves in 100 g of water at 25° C. and atmospheric pressure.

[0112] It is more preferably 3% by mass or more, further preferably 5% by mass or more, and particularly preferably 10% by mass or more.

[0113] When the solubility of the N-vinyllactam copolymer of the present disclosure in water is within the above range, it is preferred because the copolymer can be used as a carbon material dispersant in water, for example, a carbon material dispersant in a negative electrode paste for a battery.

[0114] The solubility of the N-vinyl lactam copolymer disclosed in the present invention in the electrolyte solvent is preferably 1% by mass or less. The solubility in the electrolyte solvent of 1% by mass or less means that at 25° C. and atmospheric pressure, the N-vinyl lactam copolymer disclosed in the present invention dissolves only 1 g or less per 100 g of the electrolyte solvent.

[0115] It is more preferably 0.5 mass % or less, further preferably 0.09 mass % or less, further preferably 0.07 mass % or less, still more preferably 0.05 mass % or less, and particularly preferably 0.02 mass % or less.

[0116] When the N-vinyllactam copolymer of the present disclosure is used as a battery material to produce a positive electrode and a negative electrode and assembled into a battery cell using a non-aqueous electrolyte, the amount of the copolymer dissolved and eluted into the non-aqueous electrolyte is preferably small.

[0117] The non-aqueous electrolyte solution contains an electrolyte solvent. The electrolyte solvent is not particularly limited as long as it can dissolve and disperse electrolyte salts such as various Li salts, and any solvent commonly used in batteries can be used as the electrolyte solvent.

[0118] As a non-aqueous electrolyte, a solvent with a large dielectric constant, high solubility of the above-mentioned electrolyte salt, a boiling point of 60°C or above, and a wide electrochemical stability range is preferred. An organic solvent with a low water content is more preferred. Examples of such organic solvents include: ether solvents such as ethylene glycol dimethyl ether, ethylene glycol diethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 2,6-dimethyltetrahydrofuran, tetrahydropyran, crown ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,4-dioxane, 1,3-dioxolane, etc.; chain carbonate (carbonate) solvents such as dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, diphenyl carbonate, methyl phenyl carbonate, etc.; ethylene carbonate, propylene carbonate, 2,3-dimethylethylene carbonate, 1,2-butylene carbonate and dehydrated erythritol carbonate (erythrianol carbonate) Saturated cyclic carbonate solvents such as ethylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, 2-vinylethylene carbonate and phenylethylene carbonate; fluorinated cyclic carbonate solvents such as fluoroethylene carbonate, 4,5-difluoroethylene carbonate and trifluoropropylene carbonate; aromatic carboxylic acid ester solvents such as methyl benzoate and ethyl benzoate; lactone solvents such as γ-butyrolactone, γ-valerolactone and δ-valerolactone; trimethyl phosphate Phosphate ester solvents such as acetonitrile, propionitrile, methoxypropionitrile, glutaronitrile, adiponitrile, 2-methylglutaronitrile, valeronitrile, butyronitrile, isobutyronitrile, etc.; sulfur compound solvents such as dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, cyclopentane, 3-methylcyclopentane, 2,4-dimethylcyclopentane, etc.; aromatic nitrile solvents such as benzonitrile and toluene nitrile; nitromethane, 1,3-dimethyl-2-imidazolidinone, 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone, 3-methyl-2-oxazolidinone, etc. These solvents can be used alone or in combination of two or more.

[0119] Among the electrolyte solvents, carbonate solvents such as linear carbonate solvents and cyclic carbonate solvents, lactone solvents, and ether solvents are preferred, and dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, γ-butyrolactone, γ-valerolactone, and the like are more preferred, and carbonate solvents such as dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethylene carbonate, and propylene carbonate are further preferred.

[0120] The solubility of the N-vinyl lactam copolymer disclosed in the present invention in a carbonate-based electrolyte solvent is preferably 1% by mass or less.

[0121] It is more preferably 0.5 mass % or less, further more preferably 0.09 mass % or less, further more preferably 0.07 mass % or less, particularly preferably 0.05 mass % or less, and most preferably 0.02 mass % or less.

[0122] The N-vinyl lactam copolymer disclosed herein preferably has low solubility in a mixed solvent of ethylene carbonate / ethyl methyl carbonate among the carbonate electrolyte solvents, and preferably has a solubility of 0.09 mass % or less in a mixed solvent of ethylene carbonate / ethyl methyl carbonate = 3 / 7 (mass ratio).

[0123] It is more preferably 0.07 mass % or less, further preferably 0.05 mass % or less, and particularly preferably 0.02 mass % or less.

[0124] If the solubility of the N-vinyl lactam copolymer of the present invention in a mixed solvent of ethylene carbonate / ethyl methyl carbonate = 3 / 7 (mass ratio) is within the above range, it is preferred from the perspective of being able to more fully suppress the increase in electrolyte solvent viscosity or the hindrance of battery performance caused by the dissolution of the N-vinyl lactam copolymer of the present invention from the electrode into the electrolyte solvent.

[0125] [Composition]

[0126] The composition of the present disclosure is not particularly limited as long as it contains an N-vinyllactam copolymer having a structural unit (A) derived from a salt of an acid group-containing monomer and a structural unit (B) derived from an N-vinyllactam monomer, and a carbon material.

[0127] Preferred embodiments of the N-vinyllactam-based copolymer contained in the composition of the present disclosure are as described above.

[0128] The carbon material disclosed herein is mainly conductive carbon used in the positive electrode or negative electrode of a battery, and specifically includes carbon black (ketjen black, acetylene black, etc.), graphite, carbon nanotubes (such as single-layer carbon nanotubes, multi-layer carbon nanotubes, etc.), carbon fibers (such as vapor-phase carbon fibers, etc.), and metal powder materials.

[0129] <Carbon Nanotubes>

[0130] As the carbon nanotube (hereinafter referred to as CNT) in the above-mentioned carbon material, carbon nanotubes, carbon nano protrusions, and nanographenes can be cited. Nano carbon substances are substances with a nano-sized shape containing 1 layer of hexacyclic graphite structures (graphene sheets) formed by covalent bonds of carbon atoms, and carbon nanotubes are nano carbon substances in which graphene sheets are curled and formed into a cylindrical shape. As its kind, there are single-layer carbon nanotubes (SWNT) consisting of only 1 layer, and multilayer carbon nanotubes (MWNT) with a structure formed by overlapping concentric circles of carbon nanotubes. There is no limitation on its shape, size, and manufacturing method, and carbon nanotubes of known shape, size, and manufacturing method can be used. In addition, it can also be a mixture thereof.

[0131] The length of the carbon nanotubes is not particularly limited, but is preferably 0.5 μm or more, more preferably 1 μm or more, from the viewpoint of conductivity, and is preferably 30 μm or less from the viewpoint of dispersibility.

[0132] From the perspective of making the effective ingredients of the above-mentioned CNTs have a high concentration, the content of impurities contained in the above-mentioned CNTs is preferably 40 mass% or less, more preferably 30 mass% or less, further preferably 20 mass% or less, particularly preferably 10 mass% or less, and most preferably substantially 0 mass%.

[0133] The carbon material contained in the composition of the present disclosure is preferably at least one selected from carbon black, carbon nanofibers, and carbon nanotubes.

[0134] The carbon material contained in the composition of the present disclosure is preferably the above-mentioned carbon material, since it does not adversely affect the battery performance and further improves the battery performance.

[0135] <Solvent>

[0136] The composition of the present disclosure may contain a solvent capable of dissolving the N-vinyl lactam copolymer of the present disclosure and further for dispersing the carbon material as needed.

[0137] As the above-mentioned solvent, water, a water-soluble solvent, an organic solvent or a mixed solvent thereof can be used. For example, water, an acidic aqueous solution, an alkaline aqueous solution, alcohol, ether, petroleum ether, glycol ether, cellosolve, benzene, ethyl acetate, chloroform, ketone, acetone, toluene, N-methyl-2-pyrrolidone, etc. can be cited. Among these, N-methyl-2-pyrrolidone and / or water are preferred, because other components such as the N-vinyl lactam copolymer and the binder component disclosed herein are easily dissolved, thereby improving the dispersibility of the above-mentioned carbon material.

[0138] As the above-mentioned alcohol, monohydric alcohol is preferred, monohydric alcohol with 1 to 5 carbon atoms is more preferred, and monohydric alcohol with 2 to 4 carbon atoms is further preferred, which can be straight-chain or branched. As the alcohol, methanol, ethanol, isopropanol, butanol, etc. can be cited, ethanol, isopropanol are more preferred, and isopropanol is further preferred. Considering the ease of handling and the load on the environment, it is particularly preferred to use water alone. In order to improve the wettability of the nanocarbon material (carbon nanotubes) during dispersion, to easily dissolve the nanocarbon material in a coagulated state, and to assist in the dispersion of the nanocarbon material, it is preferred to mix a hydrophilic organic solvent with water for use. The hydrophilic organic solvent is a solvent that is compatible when mixed with water, and specifically includes methanol, ethanol, propanol, isopropanol, butanol, pentanol, ethylene glycol, propylene glycol, butylene glycol, glycerol, trimethylolpropane, pentaerythritol, diethylene glycol, dipropylene glycol, triethylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monopropyl ether, diethylene glycol monobutyl ether, diethylene glycol dimethyl ether, acetone, tetrahydrofuran, N-methyl-2-pyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide, etc. These hydrophilic organic solvents may be used alone or in combination of a plurality thereof.

[0139] The content of the above-mentioned solvent contained in the composition of the present disclosure may be appropriately set according to the purpose and application, and is not particularly limited. When the total amount of the composition of the present disclosure is 100 mass %, it is preferably 1 to 99.9 mass %, more preferably 10 to 99.5 mass %, further preferably 30 to 99 mass %, and particularly preferably 50 to 98.5 mass %.

[0140] From the perspective of the dispersibility of the above-mentioned carbon material, the content of the N-vinyl lactam copolymer of the present invention contained in the composition of the present invention is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and further preferably 0.5% by mass or more, relative to 100% by mass of the composition of the present invention, and from the perspective of dispersibility, it is preferably 50% by mass or less, more preferably 40% by mass or less, and further preferably 30% by mass or less.

[0141] <Method for producing carbon material dispersion>

[0142] The composition of the present disclosure can also be made into a carbon material dispersion. For example, it can be manufactured by mixing the N-vinyl lactam copolymer of the present disclosure, the above-mentioned carbon material and the above-mentioned solvent using a known method. Therefore, one embodiment of the present disclosure relates to a method for manufacturing a carbon material dispersion made from a composition, which includes a dispersion step of mixing the N-vinyl lactam copolymer of the present disclosure, the above-mentioned carbon material and the above-mentioned solvent to disperse the above-mentioned carbon material in a liquid medium. According to the method for manufacturing a carbon material dispersion of the present disclosure, a carbon material dispersion with excellent dispersibility can be manufactured. As the carbon material and solvent used in the method for manufacturing a dispersion of the present disclosure, the same substances as the components contained in the above-mentioned composition of the present disclosure can be used.

[0143] In addition, from the perspective of easy handling, the content of the N-vinyl lactam copolymer disclosed herein is preferably 0.1% by mass to 20% by mass, more preferably 0.1% by mass to 10% by mass, and further preferably 0.3% by mass to 5% by mass, relative to 100% by mass of the carbon material dispersion. The content of the N-vinyl lactam copolymer disclosed herein in the carbon material dispersion can be determined, for example, based on the amount of raw materials charged, or by filtering out the carbon material and measuring the solid content in the solution.

[0144] In the manufacturing process of the above-mentioned dispersion, the common mixing and dispersing machine used for coating manufacturing can be used to manufacture the above-mentioned carbon material dispersion. As a mixing and dispersing machine, for example, at least one selected from ultrasonic homogenizer, vibration mill, jet mill, ball mill, bead mill, sand mill, roller mill, homogenizer, high-pressure homogenizer, ultrasonic device, stirring mill (attritor), dispersing machine (Dissolver) and coating shaker etc. can be cited. In the above-mentioned dispersion process, from the aspect of improving dispersibility, it is preferred to disperse by ultrasonic dispersion, bead mill dispersion, dispersion using emulsifying device etc. The state of the carbon material used in the dispersion can be a dry state or a state containing a liquid medium. In the above-mentioned dispersion process, the preferred mixing amount of each component can be the same as the preferred mixing ratio of the composition disclosed above.

[0145] <Method for confirming the dispersion status>

[0146] As a method for confirming the dispersibility of the above-mentioned carbon material in the carbon material dispersion of the present invention, in addition to visual inspection, it can also be implemented by the following method of measuring the absorbance of the dispersion containing the above-mentioned carbon material using a spectrophotometer. First, several samples of a dispersion with an extremely low concentration of a known carbon material concentration are prepared, the absorbance at a specific wavelength is measured, and a calibration curve of absorbance relative to concentration is prepared. Next, the above-mentioned carbon material, the above-mentioned solvent, and the N-vinyl lactam copolymer of the present invention are mixed, and after dispersion treatment is performed using a prescribed dispersion method, centrifugal separation is performed to allow the incompletely dispersed carbon material to be precipitated and separated, and the supernatant is diluted to a concentration that can be used for absorbance measurement to measure the absorbance, and the concentration is calculated according to the calibration curve. The feed amount is compared with the concentration of the dispersion according to the concentration of the obtained dispersion, thereby evaluating the dispersibility. In addition, it can also be implemented by allowing the dispersion of the composition of the present invention after centrifugation to stand for a long time and confirming the presence or absence of agglomerates.

[0147] <Carbon Nanotube Dispersed Resin Composition>

[0148] By adding a resin composition other than the N-vinyl lactam copolymer disclosed in the present invention to the carbon material dispersion liquid disclosed in the present invention, various forms of carbon material dispersion resin compositions can be obtained. As the resin composition, an existing known resin composition can be used. Specifically, a resin composition containing resins such as acrylic resins, styrene resins, olefin resins, vinyl ether resins, vinyl alcohol resins, polyester resins, polyurethane resins, polyamide resins, polycarbonate resins, polyimide resins, epoxy resins, melamine resins, phenolic resins, and silicone resins can be used. As its shape, it can be a resin solid or a resin solution thereof. A mixture of multiple resins can also be used.

[0149] The carbon material dispersion resin composition disclosed in the present invention can be used as a coating, ink, plastic, etc. formed by dispersing carbon materials. In addition to being expected to be used as a conductive material, it can also be expected to be used as an antistatic material. The preparation of a coating or ink formed by dispersing carbon materials can be achieved by implementing a method in which a resin composition is added separately according to the composition of the coating or ink to prepare the coating or ink in the carbon material dispersion of the present invention, a method in which a carbon material dispersion is added to a commercially available coating or ink, and the like. In addition, the preparation of a plastic formed by dispersing carbon materials can be achieved by implementing a method in which the carbon material dispersion of the present invention is mixed with a plastic in a molten state and the solvent is removed, a method in which the carbon material dispersion of the present invention is added to a plastic in a fine powder state and the solvent is removed or the carbon material is precipitated.

[0150] [Method for producing N-vinyl lactam copolymer]

[0151] The method for producing an N-vinyl lactam copolymer disclosed in the present invention includes a polymerization step of polymerizing a raw material monomer. The method for producing an N-vinyl lactam copolymer includes a step of polymerizing a monomer component including a salt of an acid group-containing monomer and an N-vinyl lactam monomer.

[0152] <Monomer Components>

[0153] As described above, the N-vinyllactam copolymer of the present disclosure has the structural unit (A) derived from the salt of the acid group-containing monomer and the structural unit (B) derived from the N-vinyllactam monomer as essential structural units.

[0154] The monomer corresponding to the structural unit (A) may be referred to as monomer (A). In addition, the monomer corresponding to the structural unit (B) may be referred to as monomer (B).

[0155] The monomer (A) and the monomer (B) are as described above, and preferred embodiments thereof are also the same.

[0156] In addition, as described above, the N-vinyl lactam copolymer of the present disclosure has a structural unit (A) derived from a salt of an acid group-containing monomer and a structural unit (B) derived from an N-vinyl lactam monomer as essential structural units, but may also contain a structural unit (E) derived from other monomers. The monomer corresponding to the structural unit derived from other monomers can be expressed as a monomer (E). The above-mentioned monomer (E) is as described above.

[0157] The monomers used in the above-mentioned polymerization process of the N-vinyl lactam copolymer disclosed in the present invention use the above-mentioned monomer (A) and the above-mentioned monomer (B) as essential monomers, and when the total amount of the above-mentioned monomer (A) and the above-mentioned monomer (B) is set to 100% by mass, the content (amount) of the above-mentioned monomer (A) is 30% by mass or less. If the content of the above-mentioned monomer (A) is within the above-mentioned range, the dispersibility of the carbon material is good, and the solubility in N-methyl-2-pyrrolidone is good, which is preferred from this aspect. As the amount of the above-mentioned monomer (A), it is preferably 25% by mass or less, more preferably 20% by mass or less, and further preferably 15% by mass or less.

[0158] The content of the monomer (A) is preferably 0.1% by mass or more, more preferably 1% by mass or more, and even more preferably 1.5% by mass or more, based on 100% by mass of the total amount of the monomer (A) and the monomer (B).

[0159] The use ratio of the monomer (A) within the above range is preferred from the viewpoint of being able to suppress dissolution in the electrolyte solvent.

[0160] In one embodiment, the content of the monomer (A) may be 12% by mass or less, less than 10% by mass, or 5% by mass or less.

[0161] When the content of the monomer (A) is within the above range, it is preferred from the viewpoint of good solubility in N-methyl-2-pyrrolidone.

[0162] As the monomer used in the above-mentioned polymerization step of the N-vinyllactam-based copolymer of the present disclosure, other monomers (E) other than the above-mentioned monomers (A) and (B) may be used.

[0163] When the above-mentioned other monomers (E) are used, when the total amount of the above-mentioned monomer (A), the above-mentioned monomer (B) and the other monomers (E) is set to 100% by mass, the amount of the above-mentioned monomer (E) is preferably 50% by mass or less. More preferably, it is 30% by mass or less, further preferably 20% by mass or less, and further more preferably 10% by mass or less. In one embodiment, the content of the above-mentioned monomer (E) is preferably 5% by mass or less, more preferably 2% by mass or less, and particularly preferably 0% by mass.

[0164] It should be noted that, when calculating the usage ratio of other monomers in the above-mentioned total monomer components, when other monomers have salts of amino groups, the salts of the amino groups are calculated in the form of the corresponding amino groups (amine conversion). When calculating the structure from other monomers relative to the structural units from all monomer components, and when calculating the structural units from other monomers relative to the total mass of the N-vinyl lactam copolymer of the present disclosure, the calculation is also performed by amine conversion in the corresponding case.

[0165] <Radical Polymerization Initiator>

[0166] In the polymerization of the above-mentioned monomers, a free radical polymerization initiator is preferably used. In the production method disclosed herein, especially in the above-mentioned polymerization step, as a free radical polymerization initiator, an azo polymerization initiator, hydrogen peroxide and / or an organic peroxide is preferably used. An azo polymerization initiator refers to a compound having an azo bond that generates free radicals under the action of heat or the like.

[0167] The azo polymerization initiator that can be used in the present disclosure is not particularly limited, and examples thereof include 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-bis(2-imidazolin-2-yl)[2,2'-azobispropane] dihydrochloride, 2,2'-bis(2-imidazolin-2-yl)[2,2'-azobispropane] disulfate, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] disulfate dihydrate, 2,2'-azobis(propane-2-carboxamidine) dihydrochloride, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine], 2,2'-azobis{2-[1-(2-hydroxyethyl)-2-imidazolin-2-yl]propane} dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane], 2,2'-azobis(1-imino-1-pyrrolidinyl-2-methylpropane) dihydrochloride, 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,2'-azobis[N-(2-hydroxyethyl)-2-methylpropionamide], 4,4'-azobis-4-cyanovaleric acid, azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, etc. Among these, an azo polymerization initiator having a 10-hour half-life temperature of 30° C. to 90° C. is preferred, and an azo polymerization initiator having a 10-hour half-life temperature of 40° C. to 70° C. is more preferred, because they tend to be able to efficiently produce N-vinyllactam polymers and the color tone of the obtained polymer tends to be good at high temperatures. Specifically, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-bis(2-imidazolin-2-yl)[2,2'-azobispropane] dihydrochloride, 2,2'-bis(2-imidazolin-2-yl)[2,2'-azobispropane] disulfate, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] disulfate dihydrate, 2,2'-azobis(propane-2-carboxamidine) dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane], bis(2-amidinopropane) dihydrochloride, 2,2'-bis(2-imidazolin-2-yl)[2,2'-azobispropane] dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] disulfate dihydrate, and most preferably 2,2'-azobis(2-amidinopropane) dihydrochloride.Azo polymerization initiators having a carboxyl group (such as 2,2′-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]) may adversely affect coloration, so when used as desired, they are preferably used in as small an amount as possible, and more preferably not used.

[0168] Examples of organic peroxides that can be used in the present disclosure include alkyl hydroperoxides such as tert-butyl hydroperoxide, di-tert-butyl peroxide, cumene hydroperoxide, tert-hexyl hydroperoxide, and terpene hydroperoxide; tert-butyl peroxyacetate, disuccinyl peroxide, and peracetic acid. Of these organic peroxides, organic peroxides having a 10-hour half-life temperature of 30° C. to 180° C. are preferred, and organic peroxides having a 10-hour half-life temperature of 40° C. to 170° C. are more preferred.

[0169] The free radical polymerization initiator used in the manufacturing method disclosed herein, especially in the polymerization step, preferably has one or more selected from the azo polymerization initiator and the organic peroxide as essential components, but other free radical polymerization initiators may also be used in combination. Examples of such initiators include persulfates such as sodium persulfate, potassium persulfate, and ammonium persulfate, and hydrogen peroxide.

[0170] The radical polymerization initiator used in the present invention is preferably the above-mentioned azo polymerization initiator and / or hydrogen peroxide.

[0171] Hydrogen peroxide is preferred because it is easy to reduce the molecular weight even without using a chain transfer agent such as a phosphorus compound. By lowering the molecular weight of the N-vinyl lactam copolymer, it is expected that the dispersibility will be further improved.

[0172] Unless otherwise specified, the amount of the radical polymerization initiator used (the total amount when using two or more) is preferably 0.1 to 5% by mass, more preferably 0.5 to 4% by mass, and even more preferably 1 to 3% by mass, based on the total monomer components.

[0173] When the amount of the radical polymerization initiator used is within the above range, the molecular weight of the polymer tends to be easily adjusted, and the amount of impurities is reduced, so that coloration during heating tends to be further suppressed, which is preferred.

[0174] The method for adding the polymerization initiator to the reaction system (polymerization reactor) is not particularly limited, but the polymerization initiator is preferably added continuously or stepwise. When the polymerization initiator is added continuously, the dripping speed may be varied.

[0175] The polymerization initiator may be added directly without being dissolved in a solvent, but is preferably dissolved in a solvent described later and then added to the reaction system (polymerization reactor).

[0176] When hydrogen peroxide is used as a radical polymerization initiator in the above-mentioned manufacturing method, its amount is not particularly limited, and is preferably 1.0 to 4.0% by mass relative to 100% by mass of the total monomers. This allows the polymerization reaction rate to be in a more preferred range. In addition, by making the amount of hydrogen peroxide used 1.0% by mass or more relative to 100% by mass of the total monomers, the time stability of the obtained polymer solution is improved. In addition, by making the amount of hydrogen peroxide used 4.0% by mass or less, the amount of 2-pyrrolidone as a by-product can be fully reduced, and the performance of the polymer can be fully exerted.

[0177] The amount of hydrogen peroxide used is preferably 1.2 to 3.9% by mass, more preferably 1.5 to 3.8% by mass, and even more preferably 2.0 to 3.7% by mass.

[0178] <Reducing Agent>

[0179] In the manufacturing method disclosed in the present invention, in particular, in the above-mentioned polymerization process, although not limited, a reducing agent can be used, for example, to adjust the molecular weight of the N-vinyl lactam copolymer disclosed in the present invention. The reducing agent that can be used is not particularly limited, and examples thereof include mercaptoethanol, thioglycerol, mercaptoacetic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, thiomalic acid, octyl mercaptoacetate, octyl 3-mercaptopropionic acid, 2-mercaptoethanesulfonic acid, n-dodecyl mercaptan, octyl mercaptan, butyl mercaptoacetate and other mercaptan compounds; halides such as carbon tetrachloride, dichloromethane, tribromoform, bromotrichloroethane; hydroxyl-containing compounds other than the above-mentioned alcohol compounds; phosphorous acid, phosphites, hypophosphorous acid, hypophosphites and their hydrates; lower oxides and salts thereof such as sulfurous acid, hydrogen sulfite, dithionite, pyrosulfite and their salts, and the like. These salts are metal salts of sodium, ammonium salts or organic amine salts. Two or more of the above-mentioned reducing agents can be used.

[0180] When used for special industrial applications such as production of hollow fiber membranes, or for electrical material applications such as semiconductor cleaning, it is preferred to reduce the amount of metal salts such as sodium salts as much as possible.

[0181] <Chain transfer agent>

[0182] The above-mentioned polymerization process can be implemented in the presence of a phosphorus atom-containing compound. By chain transfer to the phosphorus atom-containing compound, a substituent containing a phosphorus atom can be effectively introduced into the N-vinyl lactam copolymer of the present disclosure. And it is possible to efficiently carry out low molecular weight. Regarding the phosphorus atom-containing compound and its preferred embodiment, except for the case of special mention, hypophosphorous acid (salt), phosphorous acid (salt), phosphoric acid (salt), hypophosphite, phosphite, phosphate, etc. can be exemplified.

[0183] Hypophosphorous acid (salt), phosphorous acid (salt), and hypophosphite are preferred due to high chain transfer efficiency, and hypophosphorous acid (salt) is more preferred. When a phosphorus atom-containing compound is used, one type or two or more types may be used.

[0184] In the above polymerization step, the amount of the phosphorus atom-containing compound is preferably 0.1 g or more and 5 g or less, and more preferably 0.3 g or more and 1 g or less, relative to 1 mol of the monomer (total monomers). It should be noted that, when the phosphorus atom-containing compound is a salt, the above range is calculated in the form of the corresponding acid. For example, if it is sodium hypophosphite, the mass is calculated in the form of the corresponding acid, i.e., hypophosphorous acid.

[0185] The above-mentioned polymerization step may use a chain transfer agent other than the phosphorus atom-containing compound (hereinafter also referred to as other chain transfer agents) as desired. Examples of other chain transfer agents include mercaptan chain transfer agents such as mercaptoethanol and mercaptopropionic acid; halides such as carbon tetrachloride and dichloromethane; secondary alcohols such as isopropyl alcohol and glycerol; sulfurous acid (salts) such as sodium sulfite; hydrogen sulfite (salts) such as sodium bisulfite; dithionite (salts) such as sodium dithionite; pyrosulfite (salts) such as potassium pyrosulfite, etc. When the above-mentioned other chain transfer agents are used, they may be used alone or in combination of two or more.

[0186] <Reducing Compounds>

[0187] In the production method disclosed herein, especially in the above-mentioned polymerization step, a heavy metal ion (or heavy metal salt) may be used as a reducing compound that acts as a decomposition catalyst of the polymerization initiator. In the present invention, a heavy metal refers to a metal having a specific gravity of 4 g / cm 3 Among the heavy metals, iron and / or copper are preferred, and as the reducing compound, heavy metal salts such as Mohr's salt (Fe(NH4)2(SO4)2·6H2O), ferrous sulfate heptahydrate, ferrous chloride, iron (III) chloride, copper (I) sulfate and / or its hydrate, copper (II) sulfate and / or its hydrate, copper (II) chloride and / or its hydrate can be used.

[0188] The amount of the heavy metal compound is not particularly limited, but the amount of metal ions is preferably 0.01 to 10 ppm by mass relative to the monomer component. That is, the amount of the heavy metal compound is converted into the amount of metal ions, and is preferably 0.01 to 10 ppm by mass relative to the monomer component. As the amount of metal ions, it is more preferably 0.01 to 5 ppm by mass. This allows the decomposition rate of hydrogen peroxide to be within a preferred range.

[0189] The amount of the metal ion is preferably 0.001 to 0.35 mmol %, more preferably 0.001 to 0.21 mmol %, based on the monomer component.

[0190] When the heavy metal ions are used, they can be used in a range of 0.1 to 10 ppm, for example. However, when used for special industrial applications such as production of hollow fiber membranes or electrical material applications such as semiconductor cleaning, it is preferred not to use the heavy metal ions.

[0191] <Other additives>

[0192] In the manufacturing method disclosed in the present invention, in particular in the above-mentioned polymerization process, ammonia and / or amine compounds can be used for the purpose of promoting polymerization reaction, preventing hydrolysis of N-vinyl lactam, etc. Ammonia or amine compounds function as a catalyst promoter in the polymerization reaction. That is, if ammonia and / or amine compounds are included in the reaction system, the polymerization reaction can be further promoted compared to the case where they are not included. In addition, it can also function as an alkaline pH regulator. It should be noted that ammonia is the cause of odor and also affects coloration, so it is preferably used in a suppressed amount. When using ammonia, it can be used directly in the form of a gaseous single component at room temperature, or it can be used in the form of an aqueous solution (ammonia water). The addition of ammonia and / or amine compounds can be carried out by any appropriate method, for example, they can be put into the reaction vessel at the beginning of the polymerization, or they can be added to the reaction vessel one by one during the polymerization.

[0193] As the amine compound, any appropriate amine compound may be adopted. Specifically, primary amine, secondary amine, and tertiary amine may be mentioned. The above amine may be only one kind or two or more kinds.

[0194] Examples of the primary amine include monoethanolamine, allylamine, isopropylamine, diaminopropylamine, ethylamine, 2-ethylhexylamine, 3-(2-ethylhexyloxy)propylamine, 3-ethoxypropylamine, 3-(diethylamino)propylamine, 3-(dibutylamino)propylamine, tetramethylethylenediamine, tert-butylamine, sec-butylamine, propylamine, 3-(methylamino)propylamine, 3-(dimethylamino)propylamine, and 3-methoxypropylamine. The primary amines may be used alone or in combination of two or more.

[0195] Examples of the secondary amines include aliphatic secondary amines such as dimethylamine, diethylamine, dipropylamine, diisopropylamine, N-methylethylamine, N-methylpropylamine, N-methylisopropylamine, N-methylbutylamine, N-methylisobutylamine, N-methylcyclohexylamine, N-ethylpropylamine, N-ethylisopropylamine, N-ethylbutylamine, N-ethylisobutylamine, N-ethylcyclohexylamine, N-methylethyleneamine, and N-methylallylamine; and N-methylethylenediamine, N-ethylethylenediamine, N,N'-dimethylethylenediamine, N,N'-diethylethylenediamine, N-methyltrimethylenediamine, N-ethyltrimethylenediamine, N,N Aliphatic diamines and triamines such as '-dimethyltrimethylenediamine, N,N'-diethyltrimethylenediamine, diethylenetriamine, and dipropylenetriamine; aromatic amines such as N-methylbenzylamine, N-ethylbenzylamine, N-methylphenylethylamine, and N-ethylphenylethylamine; monoalkanolamines such as N-methylethanolamine, N-ethylethanolamine, N-propylethanolamine, N-isopropylethanolamine, N-butylethanolamine, and N-isobutylethanolamine; dialkanolamines such as diethanolamine, dipropanolamine, diisopropanolamine, and dibutanolamine; cyclic amines such as pyrrolidine, piperidine, piperazine, N-methylpiperazine, N-ethylpiperazine, morpholine, and thiomorpholine. The above-mentioned secondary amines can be used alone or in combination of two or more. Among these secondary amines, dialkanolamines and dialkylamines are preferred, dialkanolamines are more preferred, and diethanolamine is particularly preferred.

[0196] Examples of the tertiary amine include trialkanolamines such as trimethylamine, triethylamine, tripropylamine, triisopropylamine, triethanolamine, tripropanolamine, triisopropanolamine, and tributanolamine. The tertiary amines may be used alone or in combination of two or more. Among these tertiary amines, trialkanolamines are preferred, and triethanolamine is particularly preferred.

[0197] When the above-mentioned ammonia and amine compounds are used, the total amount of the two is preferably 0.01 parts by mass or more, and more preferably 0.02 to 1 parts by mass, relative to 100 parts by mass of N-vinyl lactam. Within the above range, the reaction rate tends to be increased, and the effect of suppressing the hydrolysis and coloration of N-vinyl lactam accompanying the decrease in pH during the reaction can be obtained.

[0198] When hydrogen peroxide is used as the polymerization initiator, ammonia is preferably used, and the amount used is not particularly limited, but is preferably 0.1 to 3.0% by mass, more preferably 0.15 to 2.0% by mass, and even more preferably 0.2 to 1.0% by mass, based on 100% by mass of all monomers.

[0199] It should be noted that when a copper salt is used as the heavy metal salt and ammonia is used, a copper ammonia salt can be formed. Examples of copper ammonia salts include diammine copper salts ([Cu(NH3)2]2SO4·H2O, [Cu(NH3)2]Cl, etc.) and tetraammine copper salts ([Cu(NH3)4]SO4·H2O, [Cu(NH3)4]Cl2, etc.).

[0200] When copper ammine salt is used as the heavy metal salt, the copper ammine salt may be added to the reactor, but it is preferred to add a copper salt such as copper sulfate, copper chloride, copper nitrate, copper acetate, and ammonia to the reactor to form the copper ammine salt.

[0201] When hydrogen peroxide and ammonia are used in the manufacture of the N-vinyl lactam copolymer of the present invention, ammonia and hydrogen peroxide may be further added after the addition of the monomer components is completed. The amount of ammonia and hydrogen peroxide used after the addition of the monomer components is preferably 0 to 0.3% by mass and 0.2 to 2.5% by mass, respectively, relative to 100% by mass of the total monomer amount.

[0202] <Polymerization Solvent>

[0203] The polymerization step is preferably carried out in the presence of a solvent. As the solvent, one or more selected from alcohols such as water, methanol, ethanol, isopropanol (2-propanol), n-butanol, diethylene glycol, etc. can be exemplified. As the solvent, water and isopropanol are preferred. Water is more preferred. The amount of the solvent used is preferably 40 to 1000% by mass relative to 100% by mass of the monomer.

[0204] The polymerization step is preferably carried out so that the solid content concentration (concentration of nonvolatile components in the solution) after the polymerization is 10 to 80% by mass relative to 100% by mass of the polymerization solution, more preferably 15 to 70% by mass, and even more preferably 20 to 60% by mass.

[0205] <Other polymerization conditions>

[0206] The temperature during polymerization is preferably 50° C. or higher, more preferably 55 to 100° C., and even more preferably 60 to 90° C. When the temperature during polymerization is within the above range, the residual monomer component decreases and the dispersibility of the polymer tends to improve.

[0207] The temperature during polymerization may be 70°C or higher, 75 to 110°C, or 80 to 105°C.

[0208] It should be noted that the temperature during polymerization does not always have to be kept constant during the polymerization reaction. For example, the polymerization can be started from room temperature, and the temperature can be raised to a set temperature with an appropriate heating time or heating rate, and then the set temperature can be maintained. The polymerization temperature can also be changed (heated up or cooled) over time during the polymerization reaction according to the method of adding monomer components or initiators.

[0209] The pH during polymerization is preferably 5 or more, more preferably 6 or more, and preferably 11 or less, from the viewpoint of suppressing the generation of impurities and by-products.

[0210] As the pressure in the reaction system, it can be any one of normal pressure (atmospheric pressure), reduced pressure, and pressurized. From the aspect of the molecular weight of the obtained polymer, it is preferably carried out at normal pressure or by sealing in the reaction system and under pressure. In addition, from the aspect of the equipment such as a pressure device or a pressure reducer, a pressure-resistant reaction vessel or a piping, it is preferably carried out under normal pressure (atmospheric pressure). As the atmosphere in the reaction system, it can be an air atmosphere, but it is preferably an inert atmosphere, for example, preferably before the polymerization starts, inert gases such as nitrogen are utilized to replace in the system.

[0211] The polymerization time is preferably more than 30 minutes and less than 5 hours. If the polymerization time becomes longer, there is a tendency for the coloring of the polymerization liquid to increase. After the polymerization is terminated, a aging process (referring to a process maintained under heating and heat preservation conditions after polymerization) can be provided for the purpose of reducing the monomers remaining in the polymerization liquid. The aging time is usually more than 1 minute and less than 4 hours. If a polymerization initiator (booster) is further added during the aging time, the monomers remaining in the polymerization liquid can be reduced, so it is preferred.

[0212] In the late stage of polymerization, it is preferred that the initiator addition completion time is the same as the monomer addition completion time or that the initiator addition completion time is later than the monomer addition completion time because the monomer remaining in the polymerization solution can be reduced.

[0213] <Addition of organic acid>

[0214] In the present disclosure, an organic acid or its aqueous solution may be added to the reaction solution after the polymerization reaction is completed (hereinafter referred to as an organic acid addition process). At this time, it is preferred to maintain the reaction temperature during the polymerization reaction. Thus, the residual N-vinyl lactam is hydrolyzed under the action of the acid, so that the amount of unreacted monomer (i.e., the residual amount of the monomer in the reaction solution) can be reduced. For example, if the monomer is N-vinyl-2-pyrrolidone, it is hydrolyzed into 2-pyrrolidone under the action of the acid.

[0215] As the organic acid that can be used to reduce the amount of residual monomers, a carboxylic acid having a boiling point higher than the temperature of the reaction solution when the organic acid is added (e.g., 100° C. or higher) is preferred, and specific examples thereof include formic acid, acetic acid, propionic acid, oxalic acid, malonic acid, succinic acid, aspartic acid, citric acid, glutamic acid, fumaric acid, malic acid, maleic acid, phthalic acid, trimellitic acid, pyromellitic acid, etc. These organic acids may be used alone or in combination of two or more.

[0216] The amount of the organic acid used may be appropriately adjusted according to the amount of N-vinyl lactam used during the polymerization reaction, and is not particularly limited. For example, the pH of the reaction solution after polymerization may be preferably 5 or less, more preferably 3 or more and 4 or less. Specifically, the amount of the organic acid used is preferably 100 ppm or more and 30,000 ppm or less, and more preferably 500 ppm or more and 20,000 ppm or less, relative to the amount of N-vinyl lactam used.

[0217] <Residual Monomer Amount>

[0218] According to the method for producing the N-vinyl lactam copolymer disclosed in the present invention, the amount of monomers remaining unreacted can be reduced, and thus it is preferred. The amount of residual monomers is preferably less than 200 ppm relative to the obtained N-vinyl lactam polymer disclosed in the present invention. It is more preferably less than 100 ppm, further more preferably less than 50 ppm, and particularly preferably less than 10 ppm. If the amount of residual monomers is within the above range, there is a tendency to reduce the amount of impurities, suppress coloring during heating, and suppress odor, and from this aspect it is preferred. In addition, the residual monomers are easily dissolved in the electrolyte solvent, which may hinder the battery performance, so by reducing the amount of residual monomers, the hindrance to the battery performance can be fully suppressed, and from this aspect it is preferred.

[0219] <Impurities from Monomers>

[0220] According to the method for producing the N-vinyl lactam copolymer disclosed in the present invention, the amount of impurities from the monomer can be reduced, so it is preferred. Regarding impurities from the monomer, for example, if the monomer is N-vinyl-2-pyrrolidone, the impurity is 2-pyrrolidone. The amount of impurities from the monomer is preferably 50,000 ppm or less relative to the obtained N-vinyl lactam polymer disclosed in the present invention. It is more preferably 30,000 ppm or less, further preferably 20,000 ppm or less, and particularly preferably 15,000 ppm or less. If the amount of impurities from the monomer is within the above range, it has a tendency to suppress coloring during heating and to suppress odor, which is preferred from this aspect. In addition, impurities are easily dissolved in the electrolyte solvent and may hinder battery performance. Therefore, by reducing the amount of impurities, the hindrance to battery performance can be fully suppressed, which is preferred from this aspect.

[0221] In one embodiment, the amount of impurities derived from the monomer may be 5000 ppm or less, 3000 ppm or less, 2000 ppm or less, or 1500 ppm or less.

[0222] <Drying process>

[0223] In order to obtain an N-vinyl lactam copolymer from the N-vinyl lactam copolymer solution obtained in the polymerization process, a drying process may be performed. The drying process is a process of powdering, etc., and also includes a pulverizing process. Drying and pulverizing can be performed by known common methods, for example, powders can be obtained by spray drying, freeze drying, fluidized bed drying, drum drying, belt drying, etc. When heating and drying are performed under normal pressure, the drying temperature is preferably about 100 to 250°C, and the drying time is preferably about 0.2 to 180 minutes. When drying is performed under reduced pressure, the drying temperature can be appropriately selected according to the vacuum degree. When drying an N-vinyl lactam copolymer solution having a K value of less than 60, spray drying is preferred.

[0224] <Other Processes>

[0225] In the manufacturing method disclosed in the present invention, the polymerization step is a necessary step, and the above-mentioned organic acid addition step, drying step, etc. may be optionally included, and other steps may be optionally included. For example, a refining step, a desalting step, a concentration step, a dilution step, a pH adjustment step, etc. may be included. By treating the reaction solution (polymerization solution) with a cation exchange resin, the color tone of the obtained N-vinyl lactam copolymer solution can be improved. The step of treating with a cation exchange resin can be carried out during polymerization (in parallel with the polymerization step) or after polymerization. The treatment based on the cation exchange resin in the polymerization reaction can be treated by any appropriate method. It is preferably carried out by adding a cation exchange resin to a reaction vessel in which a polymerization reaction of a monomer component is carried out. Specifically, for example, a method of adding a cation exchange resin to a reaction vessel in which a polymerization reaction is carried out to finely suspend it and then filtering it can be cited. The treatment time based on the cation exchange resin can be any appropriate time. It is preferably 1 minute to 24 hours, more preferably 3 minutes to 12 hours, and further preferably 5 minutes to 2 hours. The manufacturing method disclosed in the present invention may not include any of the above-mentioned other steps, but may also include one or more of the above-mentioned other steps.

[0226] [Application of N-vinyl lactam copolymer]

[0227] The N-vinyl lactam copolymer disclosed in the present invention and / or the composition of the present invention can be used without particular limitation as a manufacturing aid for hollow fiber membranes, a cleaning agent for semiconductors, an additive for adhesives or binders, an aid for electronic component manufacturing, a detergent additive, an additive for cosmetics, a thickener, an ink additive, a pigment dispersant, a dispersant for positive / negative electrode materials for batteries, a dispersant for inorganic particles, an additive for coating compositions, a surface treatment agent, a resin modifier, a binder for inorganic substances, a ceramic binder, an additive for inorganic compositions, a fiber treatment agent, an additive for functional fibers, and the like.

[0228] Example

[0229] The present invention is described in more detail below with reference to Examples, but the present invention is not limited to these Examples. It should be noted that, unless otherwise stated, "parts" means "parts by mass" and "%" means "% by mass".

[0230] Each evaluation of the polymer was performed by the following methods.

[0231] <Measurement of Solid Content of Polymer>

[0232] 1 g of polymer (mass W2 (g)) was weighed in a weighing pot (mass W1 (g)) with a bottom diameter of about 5 cm, and dried in a constant temperature dryer at 150°C for 1 hour. The mass of the weighing pot + polymer after drying was measured (W3 (g)), and the solid content was calculated by the following formula.

[0233] Solid content (mass %) = ((W3 (g) - W1 (g)) / W2 (g)) × 100

[0234] <Determination of K value of polymer>

[0235] Deionized water is added to the polymer and diluted in a manner that the concentration converted to solid content is 1% by mass. The viscosity of the solution is measured at 25±0.2°C using an Ubbelohde viscometer. The time it takes for the solution to flow between the two markings is measured. Several measurements are made and the average value is taken. In order to determine the relative viscosity, the deionized water is also measured in the same manner. The two flow times obtained are corrected based on the Hagenbach-Couette correction.

[0236] [Number 1]

[0237]

[0238] In the above formula, Z is the relative viscosity (ηrel) of a solution of concentration C, and C is the concentration (%: g / 100 ml).

[0239] The relative viscosity ηrel is obtained by the following formula.

[0240] [Number 2]

[0241] ηrel=(flow time of solution)÷(flow time of water)

[0242] <Measurement of Weight Average Molecular Weight (Mw) of Polymer>

[0243] The weight average molecular weight of the copolymer was determined by measuring with gel permeation chromatography (GPC) under the following conditions.

[0244] Apparatus: Alliance HPLC system manufactured by Waters

[0245] Detector: RI

[0246] Column: TSKgel α-M (2 pieces), TSKgel α

[0247] Column temperature: 40°C

[0248] Flow rate: 0.6ml / min

[0249] Calibration Curve: Polyethylene Oxide Standards

[0250] Eluent: ion exchange water / acetonitrile 84 / 16 (containing 1.4% sodium nitrate)

[0251] <Measurement of polymer pH>

[0252] Deionized water was added to the polymer to dilute it so that the concentration in terms of solid content became 5% by mass, and the pH of the solution was measured.

[0253] <Quantitative determination of N-vinylpyrrolidone and 2-pyrrolidone in polymers>

[0254] Quantitative analysis was performed by liquid chromatography under the following conditions.

[0255] Device: Shiseido "NANOSPACE SI-2" (using UV / VIS detector)

[0256] Column: Osaka Soda "CAPCELLPAK C18 UG120 (1.5 mm inner diameter, 250 mm length)", 40°C

[0257] Eluent: methanol for LC (manufactured by Wako Pure Chemical Industries, Ltd.) / ultrapure water = 1 / 24 (mass ratio), 0.04 mass% of sodium 1-heptanesulfonate added

[0258] Flow rate: 100 μL / min

[0259] <Quantitative determination of salt of acid group-containing monomer of polymer>

[0260] Quantitative analysis was performed by liquid chromatography under the following conditions.

[0261] Apparatus: Alliance HPLC system manufactured by Waters

[0262] Column: Shodex RS pak DE-413L, Shodex RS pak DE-G, 40°C, manufactured by Showa Denko K.K.

[0263] Eluent: 0.1% phosphoric acid aqueous solution

[0264] Flow rate: 1mL / min

[0265] <Evaluation of polymer solubility in N-methyl-2-pyrrolidone>

[0266] N-methyl-2-pyrrolidone (hereinafter also referred to as "NMP") was added to the polymer so as to have a concentration of 1% by mass in terms of solid content. After sufficient stirring, the solution was allowed to stand for 24 hours, and the solution after standing was visually observed and evaluated according to the following criteria.

[0267] ○: The solution is transparent and no insoluble matter is observed

[0268] ×: Insoluble matter was observed, and / or the solution was opaque

[0269] <Evaluation of polymer solubility in deionized water>

[0270] Deionized water was added to the polymer so that the concentration in terms of solid content became 1% by mass, and the mixture was stirred thoroughly and allowed to stand for 24 hours. The solution after standing was visually observed and evaluated according to the following criteria.

[0271] ○: The solution is transparent and no insoluble matter is observed

[0272] ×: Insoluble matter was observed, and / or the solution was opaque

[0273] <Evaluation of solubility of polymer in electrolyte: mixed solvent of ethylene carbonate / ethyl methyl carbonate = 3 / 7 (weight ratio)>

[0274] A mixed solvent of ethylene carbonate / ethyl methyl carbonate = 3 / 7 (weight ratio) was added to the polymer in a concentration of 0.1% by mass calculated as solid content, and stirred for 1 hour using an oscillator (ROLLER10 Digital, 80 rpm manufactured by IKA). Afterwards, the viscosity of the electrolyte was compared before and after the addition of the polymer. In addition, the supernatant was diluted to 2 times using N,N-dimethylformamide and measured using gel permeation chromatography (GPC) under the following conditions.

[0275] Device: HLC-8320GPC manufactured by Tosoh

[0276] Detector: RI

[0277] Column: Shodex KD-806M (2 pcs), KD-G 4A manufactured by Showa Denko K.K.

[0278] Column temperature: 40°C

[0279] Flow rate: 0.8ml / min

[0280] Calibration Curve: Polystyrene Standards

[0281] Eluent: N,N-dimethylformamide (containing 0.1% LiBr)

[0282] A calibration curve was drawn using polyvinyl pyrrolidone K-30 (manufactured by Nippon Shokubai) to quantify the concentration (W4 (ppm)) of the polymer in the supernatant (2-fold dilution). The dissolution rate of the polymer in the electrolyte (ethylene carbonate / ethyl methyl carbonate = 3 / 7 (weight ratio)) was calculated using the following formula.

[0283] Dissolution rate (%) = W4 (ppm) × 2 / W5 (ppm) × 100

[0284] W5 (ppm): The concentration of the polymer in the electrolyte, calculated from the amount added

[0285] In addition, the solubility of the polymer in the electrolyte solution was calculated by the following formula.

[0286] Solubility (%) = 0.1 × dissolution rate (%)

[0287] When the dissolution rate is 100%, the solubility is judged to be 0.1% or more.

[0288] (Production Example 1: Production of Polymer A)

[0289] 420 parts of deionized water were placed in a 1L reactor (made of SUS304) equipped with a large wide blade (Maxblend) stirring blade (made of SUS304), a thermometer, a reflux pipe, and a jacket. While stirring the deionized water at 250 rpm, nitrogen substitution was performed at 200 ml / min for 30 minutes to remove dissolved oxygen. Then, nitrogen was introduced at 30 ml / min, and the reactor was heated while stirring at 250 rpm to a temperature of 80°C. After the liquid temperature was stabilized at 80°C, 180 parts of N-vinyl pyrrolidone (manufactured by Nippon Shokubai, hereinafter referred to as "NVP"), 87.2 parts of a 4% aqueous solution of lithium acrylate (acrylic acid manufactured by Nippon Shokubai was neutralized with lithium hydroxide, hereinafter referred to as "AA-Li"), and 45.9 parts of a 10% aqueous solution of 2,2'-azobis(2-methylpropionamidine) dihydrochloride (manufactured by Fujifilm Wako Pure Chemical Industries, hereinafter referred to as "V-50") as a polymerization initiator were added dropwise over 120 minutes to initiate polymerization. After the 120-minute dropwise addition of the 4% aqueous solution of AA-Li was completed, 4.6 parts were then added dropwise over 30 minutes. In addition, 1.8 parts of a 10% aqueous solution of V-50 were added all at once 30 minutes after the 120-minute dropwise addition was completed. The temperature was maintained at 80°C from the start of the dropwise addition to 240 minutes to obtain an NVP / AA-Li copolymer solution.

[0290] The obtained NVP / AA-Li copolymer solution was vacuum dried at 110° C. and then pulverized until it passed through a JIS standard sieve with a mesh size of 500 μm. The powder was further vacuum dried at 110° C. to obtain an NVP / AA-Li copolymer (powder).

[0291] (Production Example 2: Production of Polymer B)

[0292] 1.28 parts of sodium hypophosphite monohydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 438 parts of deionized water were added to a 1L reactor equipped with a Maxblend type stirring blade, a thermometer, a reflux tube, and a jacket. The nitrogen replacement and heating of the solution were carried out in the same manner as in Production Example 1. After the liquid temperature was stabilized at 80°C, 180 parts of NVP, 78.3 parts of a 4% aqueous solution of sodium acrylate (acrylic acid manufactured by Nippon Catalyst Co., Ltd. was neutralized with sodium hydroxide, hereinafter also referred to as "AA-Na"), and 34.8 parts of a 10% aqueous solution of V-50 as a polymerization initiator were added dropwise over 120 minutes to initiate polymerization. After the 120-minute dropwise addition of the 4% aqueous solution of AA-Na was completed, 4.1 parts were then added dropwise over 30 minutes. In addition, 1.4 parts of the 10% aqueous solution of V-50 were added all at once 30 minutes after the 120-minute dropwise addition was completed. The temperature was maintained at 80° C. from the start of the dropwise addition until 240 minutes, thereby obtaining an NVP / AA-Na copolymer solution.

[0293] The obtained NVP / AA-Na copolymer solution was dried and pulverized by the same method as in Production Example 1 to obtain an NVP / AA-Na copolymer (powder).

[0294] (Production Example 3: Production of Polymer C)

[0295] 1.33 parts of sodium hypophosphite monohydrate and 449 parts of deionized water were added to a 1L reactor equipped with a Maxblend stirring blade, a thermometer, a reflux tube, and a jacket. The nitrogen replacement and heating of the solution were carried out in the same manner as in Preparation Example 1. After the liquid temperature was stabilized at 80°C, 180 parts of NVP, 90 parts of a 10% aqueous solution of ammonium acrylate (acrylic acid produced by Nippon Catalyst was neutralized with ammonia water, hereinafter also referred to as "AA-NH3"), and 36 parts of a 10% aqueous solution of V-50 as a polymerization initiator were added dropwise over 120 minutes to initiate polymerization. After the 120-minute dropwise addition of the 10% aqueous solution of AA-NH3 was completed, 4.8 parts were then added dropwise over 30 minutes. In addition, 1.4 parts of the 10% aqueous solution of V-50 were added at once 30 minutes after the 120-minute dropwise addition was completed. The temperature was maintained at 80°C from the start of the dropwise addition to 240 minutes to obtain an NVP / AA-NH3 copolymer solution.

[0296] The obtained NVP / AA-NH3 copolymer solution was dried and pulverized by the same method as in Production Example 1 to obtain an NVP / AA-NH3 copolymer (powder).

[0297] (Production Example 4: Production of Polymer D)

[0298] 311 parts of deionized water were added to a 1L reactor equipped with a Maxblend stirring blade, a thermometer, a reflux tube, and a jacket. The nitrogen replacement and heating of the solution were carried out in the same manner as in Preparation Example 1. After the liquid temperature was stabilized at 80°C, 150 parts of NVP, 79.2 parts of a 10% aqueous solution of AA-NH3, 79.2 parts of a 10% aqueous solution of 2-methoxyethyl acrylate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., hereinafter also referred to as "MEA"), and 41.7 parts of a 10% aqueous solution of V-50 as a polymerization initiator were added dropwise over 120 minutes to initiate polymerization. After the 120-minute dropwise addition of the 10% aqueous solution of AA-NH3 and the 10% aqueous solution of MEA, 4.2 parts were added dropwise each over 30 minutes. In addition, 1.7 parts of the 10% aqueous solution of V-50 were added all at once 30 minutes after the 120-minute dropwise addition of the 10% aqueous solution of AA-NH3. The temperature was maintained at 80°C from the start of the dropwise addition until 240 minutes, thereby obtaining an NVP / AA-NH3 / MEA copolymer solution.

[0299] The obtained NVP / AA-NH3 / MEA copolymer solution was dried and pulverized by the same method as in Production Example 1 to obtain an NVP / AA-NH3 / MEA copolymer (powder).

[0300] (Production Example 5: Production of Polymer E)

[0301] 0.33 parts of 0.05% copper sulfate aqueous solution (the amount of copper sulfate relative to NVP+AA-Na is 0.4 ppm) and 230.8 parts of deionized water were placed in a 1L reactor (SUS304) equipped with a Maxblend stirring blade (SUS304), a thermometer, a reflux tube, and a jacket. While stirring at 250 rpm, nitrogen substitution was performed at 200 ml / min for 30 minutes to remove dissolved oxygen. Then, nitrogen was introduced at 30 ml / min, and the reactor was heated while stirring at 250 rpm to a temperature of 60°C. Next, while maintaining the temperature at 60° C., 444.4 parts of a 90% NVP aqueous solution (400 parts of NVP were diluted with 44.4 parts of deionized water), 179.6 parts of a 4% AA-Na aqueous solution (19.8 parts of a 37% AA-Na aqueous solution were diluted with 163.5 parts of deionized water), 28.1 parts of a 15% hydrogen peroxide solution (16.1 parts of a 35% hydrogen peroxide solution (manufactured by Tokyo Chemical Industry Co., Ltd.) were diluted with 21.5 parts of deionized water) (the amount of hydrogen peroxide relative to NVP+AA-Na was 1.0%), and 16.0 parts of a 3% ammonia aqueous solution (2.4 parts of a 28% ammonia aqueous solution (manufactured by Wako Pure Chemical Industries, Ltd.) were diluted with 20.2 parts of deionized water) (the amount of ammonia relative to NVP+AA-Na was 0.12%) were separately added dropwise over 180 minutes.

[0302] After the sequential addition of the above raw materials was completed, 3.7 parts of a 4% AA-Na aqueous solution and 6.7 parts of a 3% ammonia aqueous solution (the amount of ammonia relative to NVP+AA-Na was 0.05%) were added dropwise over 30 minutes.

[0303] 240 minutes after the start of the dropwise addition of NVP, the temperature was raised to 80°C, and 4.8 parts of 15% hydrogen peroxide solution (the amount of hydrogen peroxide relative to NVP+AA-Na was 0.18%) was added dropwise over 30 minutes.

[0304] Next, 330 minutes after the start of NVP dropwise addition, 4.8 parts of 15% hydrogen peroxide (the amount of hydrogen peroxide relative to NVP was 0.18%) was added dropwise over 30 minutes, and the mixture was further maintained at 80°C for 1 hour to obtain an NVP / AA-Na copolymer solution.

[0305] The obtained NVP / AA-Na copolymer solution was spray-dried to obtain an NVP / AA-Na copolymer (powder).

[0306] (Production Example 6: Production of Polymer F)

[0307] A copper sulfate aqueous solution and deionized water were placed in a Maxblend type stirring blade, and nitrogen replacement and temperature increase were performed in the same manner as in Preparation Example 5. After the liquid temperature was stabilized at 60°C, 444.4 parts of a 90% NVP aqueous solution, 165.0 parts of a 4% AA-Na aqueous solution, 38.8 parts of a 25% hydrogen peroxide solution (the amount of hydrogen peroxide relative to NVP+AA-Na was 2.4%), and 21.1 parts of a 3% ammonia aqueous solution (the amount of ammonia relative to NVP+AA-Na was 0.16%) were separately added dropwise over 180 minutes.

[0308] After the sequential addition of the above raw materials was completed, 18.3 parts of a 4% AA-Na aqueous solution and 8.8 parts of a 3% ammonia aqueous solution (the amount of ammonia relative to NVP+AA-Na was 0.06%) were added dropwise over 30 minutes.

[0309] 240 minutes after the start of the dropwise addition of NVP, the temperature was raised to 80°C, and 3.4 parts of 25% hydrogen peroxide solution (the amount of hydrogen peroxide relative to NVP+AA-Na was 0.21%) was added dropwise over 30 minutes.

[0310] Next, 330 minutes after the start of NVP dropwise addition, 3.4 parts of 25% hydrogen peroxide (0.21% of hydrogen peroxide relative to NVP+AA-Na) was added dropwise over 30 minutes, and the mixture was further maintained at 80°C for 1 hour to obtain an NVP / AA-Na copolymer solution.

[0311] The obtained NVP / AA-Na copolymer solution was spray-dried to obtain an NVP / AA-Na copolymer (powder).

[0312] (Production Example 7: Production of Polymer G)

[0313] 0.34 parts of 0.05% copper sulfate aqueous solution (0.4 ppm of copper sulfate relative to monomer) and 230.4 parts of deionized water were placed in a 1L reactor equipped with a Maxblend stirring blade, a thermometer, a reflux tube, and a jacket. After the liquid temperature was stabilized at 60°C, 388.9 parts of a 90% NVP aqueous solution, 23.5 parts of a 25% hydrogen peroxide solution (the amount of hydrogen peroxide relative to the monomer was 1.4%), and 21.8 parts of a 3% ammonia aqueous solution (the amount of ammonia relative to the monomer was 0.16%) were separately added dropwise over 180 minutes, and 259.7 parts of an AA-Na / PEGMA (9) aqueous solution (20.5 parts of a 37% AA-Na aqueous solution and 63.1 parts of polyethylene glycol monomethyl ether acrylate (n=about 9) (manufactured by Tokyo Chemical Industry Co., Ltd., hereinafter also referred to as "PEGMA (9)") were diluted with 181.5 parts of deionized water) were added dropwise over 240 minutes.

[0314] After the sequential dropwise addition of NVP was completed, 9.1 parts of a 3% ammonia aqueous solution (0.06% of ammonia based on the amount of the monomer) was added dropwise over 30 minutes.

[0315] 240 minutes after the start of NVP addition, the temperature was raised to 80°C, and 5.3 parts of AA-Na / PEGMA (9) aqueous solution and 2.1 parts of 25% hydrogen peroxide (0.12% of hydrogen peroxide relative to the monomer) were added dropwise separately over 30 minutes.

[0316] Next, 330 minutes after the start of NVP addition, 2.1 parts of 25% hydrogen peroxide (0.12% of hydrogen peroxide relative to the monomer) was added dropwise over 30 minutes, and the mixture was further kept at 80°C for 1 hour to obtain an NVP / AA-Na / PEGMA (9) copolymer solution.

[0317] The obtained NVP / AA-Na / PEGMA(9) copolymer solution was spray-dried to obtain an NVP / AA-Na / PEGMA(9) copolymer (dried product).

[0318] (Production Example 8: Production of Polymer H)

[0319] 0.35 parts of 0.05% copper sulfate aqueous solution (0.4 ppm of copper sulfate relative to the monomer) and 245.2 parts of deionized water were placed in a 1L reactor equipped with a Maxblend type stirring blade, a thermometer, a reflux tube, and a jacket. The solution was replaced with nitrogen and heated in the same manner as in Production Example 5. After the liquid temperature was stabilized at 60°C, 400.0 parts of 90% NVP aqueous solution, 231.7 parts of AA-Na / PEGMA (9) aqueous solution (21.1 parts of 37% AA-Na aqueous solution and 64.9 parts of PEGMA (9) were diluted with 186.6 parts of deionized water), 25.3 parts of 15% hydrogen peroxide (0.88% of hydrogen peroxide relative to the monomer), and 22.4 parts of 3% ammonia aqueous solution (0.16% of ammonia relative to the monomer) were added dropwise over 180 minutes.

[0320] After the sequential addition of the above raw materials was completed, 40.9 parts of AA-Na / PEGMA (9) aqueous solution was added dropwise over 90 minutes, and 9.3 parts of 3% ammonia aqueous solution (0.06% ammonia based on the amount of the monomer) was added dropwise over 30 minutes.

[0321] 240 minutes after the start of the dropwise addition of NVP, the temperature was raised to 80°C, and 2.2 parts of 15% hydrogen peroxide solution (0.08% of hydrogen peroxide based on the amount of the monomer) was added dropwise over 30 minutes.

[0322] Next, 330 minutes after the start of NVP addition, 2.2 parts of 15% hydrogen peroxide (0.08% of hydrogen peroxide relative to the monomer) was added dropwise over 30 minutes, and the mixture was further kept at 80°C for 1 hour to obtain an NVP / AA-Na / PEGMA (9) copolymer solution.

[0323] The obtained NVP / AA-Na / PEGMA(9) copolymer solution was vacuum dried to obtain an NVP / AA-Na / PEGMA(9) copolymer (dried product).

[0324] (Production Example 9: Production of Polymer I)

[0325] 0.31 parts of 0.05% copper sulfate aqueous solution (0.4 ppm of copper sulfate relative to monomer) and 216.8 parts of deionized water were placed in a 1L reactor equipped with a Maxblend stirring blade, a thermometer, a reflux tube, and a jacket. After the liquid temperature was stabilized at 60°C, 311.1 parts of a 90% NVP aqueous solution, 330.2 parts of an AA-Na / PEGMA (13) aqueous solution (18.6 parts of a 37% AA-Na aqueous solution and 95.6 parts of polyethylene glycol monomethyl ether acrylate (n=about 13) (manufactured by Tokyo Chemical Industry Co., Ltd., hereinafter also referred to as "PEGMA (13)") were diluted with 274.3 parts of deionized water), 21.3 parts of a 25% hydrogen peroxide solution (the amount of hydrogen peroxide relative to the monomer was 1.4%), and 19.8 parts of a 3% ammonia aqueous solution (the amount of ammonia relative to the monomer was 0.16%) were separately added dropwise over 180 minutes.

[0326] After the sequential addition of the above raw materials was completed, 58.3 parts of AA-Na / PEGMA (13) aqueous solution was added dropwise over 90 minutes, and 8.3 parts of 3% ammonia aqueous solution (0.06% ammonia based on the amount of the monomer) was added dropwise over 30 minutes.

[0327] 240 minutes after the start of the dropwise addition of NVP, the temperature was raised to 80°C, and 1.9 parts of 25% hydrogen peroxide solution (0.12% of hydrogen peroxide relative to the amount of the monomer) was added dropwise over 30 minutes.

[0328] Next, 330 minutes after the start of NVP addition, 1.9 parts of 25% hydrogen peroxide (0.12% of hydrogen peroxide relative to the monomer) was added dropwise over 30 minutes, and the mixture was further kept at 80°C for 1 hour to obtain an NVP / AA-Na / PEGMA (13) copolymer solution.

[0329] The obtained NVP / AA-Na / PEGMA(13) copolymer solution was vacuum dried to obtain NVP / AA-Na / PEGMA(13) copolymer (dried product).

[0330] Polymer J: Polyvinyl pyrrolidone K-30 (manufactured by Nippon Shokubai)

[0331] Polymer K: Polyvinylpyrrolidone (manufactured by Aldrich, product name: PVP-360, average mol wt 360,000)

[0332] (Production Example 10: Production of Polymer L)

[0333] An NVP / AA-Li copolymer (powder) was obtained in the same manner as in Production Example 1 except that the copolymerization ratio of NVP / AA-Li was changed to 76 / 24.

[0334] (Production Example 11: Production of Polymer M)

[0335] An NVP / AA-NH3 copolymer (powder) was obtained in the same manner as in Production Example 1 except that AA-Li was changed to AA-NH3 and the copolymerization ratio of NVP / AA-NH3 was changed to 80 / 20.

[0336] (Examples 1 to 9, Comparative Examples 1 to 4)

[0337] For polymers A to M, K value, weight average molecular weight (Mw), pH, amount of N-vinylpyrrolidone and 2-pyrrolidone, and amount of (meth)acrylate were measured by the above-mentioned method. In addition, solubility evaluation in NMP, deionized water, and electrolyte (ethylene carbonate / ethyl methyl carbonate = 3 / 7 (weight ratio)) was carried out by the above-mentioned method.

[0338] In addition, polymers J and K were additionally evaluated as follows.

[0339] <Evaluation 2 of the solubility of polymer in electrolyte: mixed solvent of ethylene carbonate / ethyl methyl carbonate = 3 / 7 (weight ratio)>

[0340] The solubility evaluation of the polymers in the mixed solvent of the electrolyte solution was carried out in the same manner as above except that a mixed solvent of ethylene carbonate / ethyl methyl carbonate = 3 / 7 (weight ratio) was added to polymers J and K so that the concentration in terms of solid content became 1.2 mass %.

[0341] The dissolution rate of the copolymer in the electrolyte (ethylene carbonate / ethyl methyl carbonate = 3 / 7 (weight ratio)) was determined, and the dissolution rate of both polymers J and K was 100%. That is, it was confirmed that the solubility of both polymers J and K was 1.2% or more.

[0342] The results are shown in Tables 1 and 2.

[0343]

[0344] [Table 2]

[0345]

[0346] The above results show that polyvinyl pyrrolidone (Comparative Examples 1 and 2) is soluble in NMP and water, and is also soluble in the electrolyte at more than 1.2%, but the viscosity of the electrolyte is increased. The NVP / AA salt copolymer of the present invention (Examples 1 to 9) maintains solubility in NMP and water, while reducing dissolution in the electrolyte, and can inhibit the increase in electrolyte viscosity. It is believed that the increase in the viscosity of the electrolyte solvent, for example, in the case of battery use, will hinder battery performance. In addition, if the copolymerization ratio of AA salt is greater than 15% by mass (Comparative Examples 3 and 4), it will not dissolve in the electrolyte, but the solubility in NMP will also disappear. When NMP is used as a solvent (for example, when mixed in the positive electrode slurry for battery use), it cannot be mixed, and a bad situation occurs. In addition, the K value of the copolymer of Comparative Examples 3 and 4 is greater than 60, and it dissolves in water, but the viscosity of water is observed to increase, and a bad situation occurs.

[0347] (Examples 10 to 29, Comparative Examples 5 to 22)

[0348] Add deionized water or NMP 80g, polymer A ~ M 0.5 mass% in a 110ml screw tube, stir with a stirring piece (2.5cm). Add 0.05 mass% of carbon nanotubes (VGCF-H (registered trademark, Showa Denko Co., Ltd., fiber diameter: about 150nm, fiber length: 10 ~ 20μm multilayer carbon nanotubes, hereinafter also referred to as "CNT") or carbon black (Mitsubishi Carbon Black #10, hereinafter also referred to as "CB") to the polymer solution, stir for 1 minute (stirring speed of magnetic stirrer: HIGH, Memory9) and then stand for 1 day, visually evaluate the dispersion stability after standing. In Comparative Examples 5 to 6, 14 to 15, no polymer was added, and the same method was used for evaluation.

[0349] The evaluation criteria are as follows.

[0350] 0: The top is black, and you can't see through the back

[0351] ×: The supernatant is almost transparent, and you can see through the back

[0352] The results of the CNT dispersion are shown in Tables 3 and 4, and the results of the CB dispersion are shown in Tables 5 and 6.

[0353]

[0354]

[0355]

[0356]

[0357] The above results show that in the absence of polymer addition (Comparative Examples 5, 6, 14, 15), CNT and CB settle or suspend within 1 day and become a nearly transparent solution; while the NVP / AA salt copolymer of the present invention (Examples 10 to 29) and low molecular weight polyvinyl pyrrolidone (Comparative Examples 7, 8, 16, 17) maintain a good dispersion state of CNT and CB even after 1 day. On the other hand, it shows that high molecular weight polyvinyl pyrrolidone (Comparative Examples 9, 18) cannot maintain the dispersion state of CNT and CB after 1 day. In the case of low CB and CNT concentrations such as this dispersion, it can be said that low molecular weight polyvinyl pyrrolidone and the N-vinyl lactam copolymer disclosed in the present invention are better. In addition, the solubility of polymers L to M in NMP solvent is less than 1%, so it can be seen that they do not contribute to the dispersibility of CNT and CB in NMP solvent (Comparative Examples 11, 13, 20, 22). In addition, it was found that polymers L to M did not contribute to the dispersibility of CNT and CB in water (Comparative Examples 10, 12, 19, and 21).

[0358] Furthermore, after the condition was confirmed after the polymers were left to stand for 268 hours, it was confirmed that the dispersibility of polymers G to I was better than that of the others. It is considered that the dispersion stability was further improved by the steric repulsion effect of PEGMA copolymerized as the third component.

[0359] (Examples 30-31, Comparative Example 23)

[0360] 0.2 g (0.5% by mass) of polymer B and G were weighed in a 50 ml screw tube, respectively, and deionized water was added to make it 40 g. The polymer aqueous solution was stirred with a stirring piece (2.5 cm) to confirm that the polymer was dissolved. Then, 0.02 g (0.05% by mass) of carbon nanotubes (hereinafter also referred to as "CNT") was added to the polymer aqueous solution and stirred (stirring speed of magnetic stirring bar: Memory 5) for more than 24 hours.

[0361] It should be noted that the types of CNTs used are as follows.

[0362] ·CNT-2: K-Nanos300T, manufactured by Kumho Petrochemical, fiber diameter: multi-walled carbon nanotubes with a diameter of 10-15 nm

[0363] The mixture was then left to stand, and the dispersion stability after a certain period of time was visually evaluated.

[0364] In Comparative Example 23, no polymer was added and the evaluation was performed in the same manner.

[0365] It was confirmed that: in Comparative Example 23, without adding a polymer, after standing for 1 minute, it became ×: the supernatant was nearly transparent and could be seen through (most of it had settled). In contrast, Examples 30 and 31 to which polymers B and G were added also maintained a 0: the supernatant was black and could not be seen through (uniformly dispersed) after 1 week (168 hours).

[0366] Furthermore, after the condition was confirmed for 336 hours after the condition was further left to stand, it was confirmed that the polymer G had better dispersibility than the polymer B. It is considered that the dispersion stability was further improved by the steric repulsion effect of PEGMA copolymerized as the third component.

[0367] (Example 32, Comparative Example 24)

[0368] 0.02 g (0.05% by mass) of polymer G (Example 32) and polymer J (Comparative Example 24) were weighed in a 50 ml screw tube, respectively, and deionized water was added to make it 40 g. The polymer aqueous solution was stirred with a stirring piece (2.5 cm) to confirm that the polymer was dissolved. Then, 0.02 g (0.05% by mass) of carbon nanotubes (hereinafter also referred to as "CNT") was added to the polymer aqueous solution and stirred (stirring speed of the magnetic stirrer: Memory 5) for more than 24 hours.

[0369] It should be noted that the types of CNTs used are as follows.

[0370] ·CNT-2: K-Nanos300T, manufactured by Kumho Petrochemical, fiber diameter: multi-walled carbon nanotubes with a diameter of 10-15 nm

[0371] The mixture was then left to stand, and dispersion stability after 5 hours was visually evaluated.

[0372] It was confirmed that: Comparative Example 24 became a state of △: the supernatant was almost transparent, but the back could not be seen through (two-layer separation was confirmed), on the contrary, Example 32 with the addition of polymer G maintained a state of 0: the supernatant was black and the back could not be seen through (uniform dispersion).

[0373] It was confirmed that the dispersant of the present disclosure has good dispersion stability even when the amount of the dispersant is reduced.

[0374] (Production Examples 12 to 14)

[0375] NVP / AA-Na copolymers (powder) (polymers N, O, P) were obtained in the same manner as in Production Example 6 except that the copolymerization ratio of NVP / AA-Na was changed to 95 / 5, 90 / 10, and 85 / 15 relative to Polymer F.

[0376] (Examples 33 to 38, Comparative Example 25)

[0377] The dispersibility of polymers B, E, J, N, O, and P was evaluated by the following method.

[0378] 0.38 g (0.75%) of polymer, 2.5 g (5%) of CNT-2, and 47.1 g of deionized water were weighed in terms of solid content, stirred at 2000 rpm for 10 minutes using an autorotating and orbiting mixer, and then dispersed using an ultrasonic homogenizer for 20 minutes while cooling.

[0379] The viscosity after standing for 3 days was measured using an E-type viscometer.

[0380] Spindle 51, rotation speed 0.5~250rpm

[0381] The results are shown in Tables 7 and 8.

[0382] [Table 7]

[0383]

[0384] [Table 8]

[0385]

[0386] From the results in Table 8, it is understood that, when a hydrogen peroxide-based initiator (Example 38) is used in the production of a polymer, the viscosity can be reduced even for a high molecular weight polymer, that is, the dispersibility (stability) becomes better.

[0387] (Production Examples 15 and 16: Production of Polymers Q and R)

[0388] NVP / AA-Na copolymer (powder) (polymer Q) was obtained in the same manner as in Production Example 6 except that the copolymerization ratio of NVP / AA-Na was changed to 85 / 15 relative to polymer F and the amount of hydrogen peroxide was reduced to 64% relative to the amount in polymer F (100%).

[0389] NVP / AA-Na copolymer (powder) (polymer R) was obtained in the same manner as in Production Example 6 except that the copolymerization ratio of NVP / AA-Na was changed to 80 / 20 relative to polymer F and the amount of hydrogen peroxide was increased to 147% relative to 100% in polymer F.

[0390] (Production Example 17: Production of Polymer S)

[0391] 0.38 parts of 0.05% copper sulfate aqueous solution (the amount of copper sulfate relative to NVP+AMPS-Na is 0.4 ppm) and 263.7 parts of deionized water were placed in a 1L reactor (made of SUS304) equipped with a Maxblend type stirring blade (made of SUS304), a thermometer, a reflux tube, and a jacket. While stirring at 250 rpm, nitrogen substitution was performed at 200 ml / min for 30 minutes to remove dissolved oxygen. Then, nitrogen was introduced at 30 ml / min, and the reactor was heated at 250 rpm to a temperature of 60°C. After the liquid temperature was stabilized at 60°C, 477.8 parts of a 90% NVP aqueous solution, 135.4 parts of a 30% AMPS-Na (sodium 2-acrylamide-2-methyl-1-propane sulfonate) aqueous solution, 33.3 parts of a 20% hydrogen peroxide solution (the amount of hydrogen peroxide relative to NVP+AMPS-Na is 1.4%), and 24.7 parts of a 3% ammonia aqueous solution (the amount of ammonia relative to NVP+AMPS-Na is 0.16%) were separately added dropwise over a period of 180 minutes.

[0392] After the successive addition of the above raw materials was completed, 23.9 parts of a 30% AMPS-Na aqueous solution was added dropwise over 90 minutes, and 10.3 parts of a 3% ammonia aqueous solution was added dropwise over 30 minutes (the amount of ammonia relative to NVP+AMPS-Na was 0.06%).

[0393] 240 minutes after the start of the dropwise addition of NVP, the temperature was raised to 80°C, and 2.9 parts of 20% hydrogen peroxide (the amount of hydrogen peroxide relative to NVP+AMPS-Na was 0.12%) was added dropwise over 30 minutes.

[0394] Next, 330 minutes after the start of NVP addition, 2.9 parts of 20% hydrogen peroxide (0.12% of hydrogen peroxide relative to NVP+AMPS-Na) was added dropwise over 30 minutes, and the mixture was further kept at 80°C for 1 hour to obtain an NVP / AMPS-Na copolymer solution.

[0395] (Production Example 18: Production of Polymer T)

[0396] 0.37 parts of 0.05% copper sulfate aqueous solution (the amount of copper sulfate relative to NVP+AMPS-Na is 0.4 ppm) and 242.5 parts of deionized water were placed in a 1L reactor (made of SUS304) equipped with a Maxblend type stirring blade (made of SUS304), a thermometer, a reflux tube, and a jacket. While stirring at 250 rpm, nitrogen substitution was performed at 200 ml / min for 30 minutes to remove dissolved oxygen. Then, nitrogen was introduced at 30 ml / min, and the reactor was heated at 250 rpm to a temperature of 60°C. After the liquid temperature was stabilized at 60°C, 400.0 parts of a 90% NVP aqueous solution, 173.3 parts of a 45% AMPS-Na aqueous solution, 28.0 parts of a 25% hydrogen peroxide solution (the amount of hydrogen peroxide relative to NVP+AMPS-Na is 1.5%), and 23.7 parts of a 3% ammonia aqueous solution (the amount of ammonia relative to NVP+AMPS-Na is 0.16%) were added dropwise separately over a period of 180 minutes.

[0397] After the sequential addition of the above raw materials was completed, 43.3 parts of a 45% AMPS-Na aqueous solution was added dropwise over 90 minutes, and 9.9 parts of a 3% ammonia aqueous solution was added dropwise over 30 minutes (the amount of ammonia relative to NVP+AMPS-Na was 0.06%).

[0398] 240 minutes after the start of the dropwise addition of NVP, the temperature was raised to 80°C, and 2.5 parts of 25% hydrogen peroxide (the amount of hydrogen peroxide relative to NVP+AMPS-Na was 0.14%) was added dropwise over 20 minutes.

[0399] Next, 330 minutes after the start of NVP dropwise addition, 2.5 parts of 25% hydrogen peroxide (0.14% of hydrogen peroxide relative to NVP+AMPS-Na) was added dropwise over 20 minutes, and the mixture was further maintained at 80°C for 1 hour to obtain an NVP / AMPS-Na copolymer solution.

[0400] (Production Example 19: Production of Polymer U)

[0401] 0.36 parts of 0.05% copper sulfate aqueous solution (the amount of copper sulfate relative to NVP+AA-Na+AN is 0.4 ppm) and 182.5 parts of deionized water were placed in a 1L reactor (SUS304) equipped with a Maxblend stirring blade (SUS304), a thermometer, a reflux tube, and a jacket. While stirring at 250 rpm, nitrogen substitution was performed at 200 ml / min for 30 minutes to remove dissolved oxygen. Then, nitrogen was introduced at 30 ml / min, and the reactor was heated while stirring at 250 rpm to a temperature of 60°C. After the liquid temperature was stabilized at 60°C, a solution of 380.0 parts of NVP, 27.4 parts of acrylonitrile (hereinafter also referred to as "AN"), and 42.2 parts of deionized water, 195.2 parts of 20% AA-Na aqueous solution, 43.4 parts of 25% hydrogen peroxide (the amount of hydrogen peroxide relative to NVP+AA-Na+AN is 2.4%), and 23.6 parts of 3% ammonia aqueous solution (the amount of ammonia relative to NVP+AA-Na+AN is 0.16%) were added dropwise separately over 180 minutes.

[0402] After the successive addition of the above raw materials was completed, 48.8 parts of a 20% AA-Na aqueous solution was added dropwise over 90 minutes, and 9.8 parts of a 3% ammonia aqueous solution was added dropwise over 30 minutes (the amount of ammonia relative to NVP+AA-Na+AN was 0.06%).

[0403] 240 minutes after the start of the dropwise addition of NVP, the temperature was raised to 80°C, and 3.8 parts of 25% hydrogen peroxide (the amount of hydrogen peroxide relative to NVP+AA-Na+AN was 0.21%) was added dropwise over 30 minutes.

[0404] Next, 330 minutes after the start of NVP addition, 3.8 parts of 25% hydrogen peroxide (0.21% of hydrogen peroxide relative to NVP+AA-Na+AN) was added dropwise over 30 minutes, and the mixture was further maintained at 80°C for 1 hour to obtain an NVP / AA-Na / AN copolymer solution.

[0405] (Examples 39 to 45, Comparative Example 26)

[0406] The dispersibility of polymers O, P, Q, R, S, T, U, and J was evaluated by the following method.

[0407] 0.5 g (1.0%) of polymer, 3.0 g (6%) of CNT-2, and 46.5 g of deionized water were weighed in terms of solid content, stirred at 2000 rpm for 10 minutes using an autorotating and orbiting mixer, and then dispersed using an ultrasonic homogenizer for 20 minutes while cooling.

[0408] The viscosity immediately after the dispersion treatment and after standing at 50° C. for 1 day was measured using an E-type viscometer.

[0409] Spindle 51, rotation speed 0.5~250rpm

[0410] The results are shown in Table 9.

[0411] [Table 9]

[0412]

[0413] Even when AA-Na was changed to AMPS-Na, the carbon dispersibility was good, but AA-Na had better dispersion stability. In addition, when AN was copolymerized as the third component, a tendency for better dispersion stability was observed.

Claims

1. An N-vinyl lactam copolymer, comprising: Structural units (A) derived from salts of acid group-containing monomers, and Structural unit (B) derived from N-vinyl lactam monomer, When the total amount of the structural unit (A) and the structural unit (B) is 100% by mass, The content of the structural unit (A) is 30% by mass or less, The weight average molecular weight of the N-vinyl lactam copolymer is 1,000 or more and 100,000 or less, The K value obtained based on the Fikentscher method is 12 to 60.

2. The N-vinyl lactam copolymer according to claim 1, wherein The structural unit (A) derived from a salt of an acid group-containing monomer is a structural unit (A1) derived from a salt of a carboxyl group-containing monomer and / or a structural unit (A2) derived from a salt of a sulfonic acid group-containing monomer.

3. The N-vinyl lactam copolymer according to claim 2, wherein When the structural unit (A) contains the structural unit (A1), the content of the structural unit (A1) is 15% by mass or less based on 100% by mass of the total amount of the structural unit (A) and the structural unit (B).

4. The N-vinyl lactam copolymer according to claim 2, wherein When the structural unit (A) contains the structural unit (A2), the content of the structural unit (A2) is 30% by mass or less based on 100% by mass of the total amount of the structural unit (A) and the structural unit (B).

5. The N-vinyl lactam copolymer according to any one of claims 1 to 4, wherein The solubility of the N-vinyl lactam copolymer in water is 1% by mass or more.

6. The N-vinyl lactam copolymer according to any one of claims 1 to 5, wherein The solubility of the N-vinyl lactam copolymer in the electrolyte solvent is 1 mass % or less.

7. The N-vinyl lactam copolymer according to any one of claims 1 to 6, wherein The weight average molecular weight of the N-vinyl lactam copolymer is 5,000 or more and 100,000 or less.

8. The N-vinyl lactam copolymer according to any one of claims 1 to 7, wherein The structural unit (A1) derived from a salt of a carboxyl group-containing monomer is a structural unit derived from at least one compound selected from the group consisting of lithium acrylate, sodium acrylate, potassium acrylate, and ammonium acrylate.

9. The N-vinyl lactam copolymer according to any one of claims 1 to 8, wherein The structural unit (A2) derived from the salt of a sulfonic acid group-containing monomer is a structural unit derived from at least one compound selected from the group consisting of sodium 2-acrylamide-2-methyl-1-propane sulfonate, lithium 2-acrylamide-2-methyl-1-propane sulfonate, potassium 2-acrylamide-2-methyl-1-propane sulfonate, ammonium 2-acrylamide-2-methyl-1-propane sulfonate, sodium 2-hydroxy-3-allyloxypropane sulfonate, lithium 2-hydroxy-3-allyloxypropane sulfonate, potassium 2-hydroxy-3-allyloxypropane sulfonate, ammonium 2-hydroxy-3-allyloxypropane sulfonate, sodium 2-sulfoethyl methacrylate, lithium 2-sulfoethyl methacrylate, potassium 2-sulfoethyl methacrylate, ammonium 2-sulfoethyl methacrylate, sodium vinyl sulfonate, lithium vinyl sulfonate, potassium vinyl sulfonate, ammonium vinyl sulfonate, sodium p-styrene sulfonate, lithium p-styrene sulfonate, potassium p-styrene sulfonate, and ammonium p-styrene sulfonate.

10. A composition comprising an N-vinyl lactam copolymer and a carbon material, wherein the N-vinyl lactam copolymer has: Structural units (A) derived from salts of acid group-containing monomers, and The structural unit (B) is derived from an N-vinyllactam monomer.

11. The composition according to claim 10, wherein Contains N-methyl-2-pyrrolidone and / or water.

12. The composition according to claim 10 or 11, wherein The carbon material is at least one selected from carbon black, carbon nanofibers, and carbon nanotubes.

13. The composition according to any one of claims 10 to 12, wherein The structural unit (A) derived from a salt of an acid group-containing monomer is a structural unit (A1) derived from a salt of a carboxyl group-containing monomer and / or a structural unit (A2) derived from a salt of a sulfonic acid group-containing monomer.

14. The composition according to any one of claims 10 to 13, wherein The structural unit (A) derived from a salt of an acid group-containing monomer is a structural unit (A1) derived from a salt of a carboxyl group-containing monomer.

15. A method for producing an N-vinyl lactam copolymer, which is a method for producing the N-vinyl lactam copolymer according to any one of claims 1 to 9, wherein: The production method includes a step of polymerizing monomer components including a salt of an acid group-containing monomer and an N-vinyl lactam monomer.

Citation Information

Patent Citations

  • Dispersant for carbon material

    JP2016065142A

  • Positive electrode paste for battery

    JP2018170218A